Transfer film, method for manufacturing laminate, and method for manufacturing touch panel
By using a temporary support, a photosensitive resin layer and a protective film having a specific surface roughness in the transfer film of the touch panel, the problem of deterioration of stamping processability and poor peeling after curing of the photosensitive resin layer is solved, and better stamping processability and peeling properties are achieved.
Patent Information
- Application Number
- CN202411717947.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-12
- Filing Date
- 2020-06-09
- Publication Date
- 2025-03-14
AI Technical Summary
After curing the photosensitive resin layer of the transfer film of the conventional touch panel, the stamping processability becomes poor, and the peeling properties of the temporary support and the protective film are poor.
A transfer film structure is adopted for a temporary support, a photosensitive resin layer and a protective film having a predetermined surface roughness, wherein the cured film of the photosensitive resin layer has an elongation of breaking at 120°C of more than 15%, and the surface roughness of the temporary support and protective film is 50 nm and 150 nm or less.
The stamping processability of the transfer film and the peeling properties of the temporary support and the protective film are improved, and the excellent performance of the photosensitive resin layer is ensured.
Smart Images

Figure CN119620546A_ABST
Abstract
Description
[0001] This application is a divisional application of the application number 202080045617.9 filed by the applicant and the invention name is “Transfer film, laminate manufacturing method and touch panel manufacturing method”. The filing date of the parent case of this application is June 9, 2020, and the priority date is July 12, 2019. Technical Field
[0002] The present invention relates to a transfer film, a method for producing a laminate, and a method for producing a touch panel. Background Art
[0003] In display devices of electronic devices (for example, mobile phones, car navigation systems, personal computers, ticket machines, bank terminals, etc.), touch panels are often used as input devices.
[0004] It is known that in such a touch panel, a protective film is provided for protecting electrodes including metal wiring.
[0005] For example, Patent Document 1 describes a composition for forming a touch panel electrode protective film, which is characterized in that it contains a compound represented by Formula 1 as component A, a binder polymer as component B, and a photopolymerization initiator as component C ([Claim 1]), and describes a method for providing a photosensitive resin layer on a substrate having an electrode for a touch panel using a transfer film having a temporary support and a photosensitive resin layer composed of the composition for forming a touch panel electrode ([Claim 6][Claim 10]).
[0006] Q 2 -R 1 -Q 1 (1)
[0007] In formula (1), Q 1 and Q 2 Each independently represents a (meth)acryloyloxy group or a (meth)acryloyloxyalkyl group, and R 1 It represents a divalent hydrocarbon group.
[0008] In addition, Patent Document 2 describes a composition for forming a touch panel electrode protective film, which is characterized in that it contains a compound represented by Formula 1 as component A, a binder polymer as component B, a photopolymerization initiator as component C, and a monomer having a carboxyl group as component D, and the content of component A is 5% by mass or more and less than 50% by mass relative to the total mass of the monomer components ([Claim 1]), and describes a method for providing a photosensitive resin layer on a substrate having an electrode for a touch panel using a transfer film having a temporary support and a photosensitive resin layer composed of the composition for forming a touch panel electrode ([Claim 6][Claim 10]).
[0009] Previous technical literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2016-051470
[0012] Patent Document 2: Japanese Patent Application Publication No. 2016-155978 Summary of the invention
[0013] Technical issues to be solved by the invention
[0014] The present inventors have studied the transfer films described in Patent Documents 1 and 2, and found that the punching workability after curing may deteriorate depending on the type of the photosensitive resin layer.
[0015] Furthermore, the present inventors have found that when an attempt is made to improve the punching workability by increasing the elongation at break of the photosensitive resin layer after curing, the releasability of the temporary support and the protective film of the transfer film may deteriorate.
[0016] Therefore, an object of the present invention is to provide a transfer film, a method for producing a laminate, and a method for producing a touch panel, which have excellent releasability of a temporary support and a protective film and excellent punching workability of a cured film obtained by curing a transferred photosensitive resin layer.
[0017] Means for solving technical problems
[0018] As a result of intensive research conducted by the inventors of the present invention to achieve the above-mentioned problems, they have discovered that, with respect to a transfer film which sequentially comprises a temporary support body having a specified surface roughness, a photosensitive resin layer having a specified elongation at break at 120°C after curing, and a protective film having a specified surface roughness, the temporary support body and the protective film have excellent releasability, and the cured film formed by curing the transferred photosensitive resin layer also has excellent stamping workability, thereby completing the present invention.
[0019] That is, the present inventors have found that the above-mentioned subject can be achieved by the following configuration.
[0020] [1] A transfer film comprising, in order, a temporary support, a photosensitive resin layer and a protective film, wherein a cured film formed by curing the photosensitive resin layer has an elongation at break of 15% or more at 120°C, an arithmetic mean roughness Ra of a surface on the photosensitive resin layer side of the temporary support is less than 50 nm, and an arithmetic mean roughness Ra of a surface on the photosensitive resin layer side of the protective film is less than 150 nm.
[0021] [2] The transfer film according to [1], which satisfies the following formula (1).
[0022] X×Y<750 Formula (1)
[0023] Here, in formula (1), X represents the breaking elongation value (%) at 120° C. of a cured film obtained by curing the photosensitive resin layer, and Y represents the arithmetic mean roughness Ra value (nm) of the surface of the temporary support on the photosensitive resin layer side.
[0024] [3] The transfer film according to [1] or [2], which satisfies the following formula (2).
[0025] Y≤Z Formula (2)
[0026] Here, in formula (2), Y represents the value (nm) of the arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of the temporary support, and Z represents the value (nm) of the arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of the protective film.
[0027] [4] The transfer film according to any one of [1] to [3], wherein a cured film obtained by curing the photosensitive resin layer has a moisture permeability of 500 g / m at a film thickness of 40 μm. 2 / 24hr or less.
[0028] [5] The transfer film according to any one of [1] to [4], wherein the elongation at break at 120° C. is at least twice as large as the elongation at break at 23° C. of a cured film obtained by curing the photosensitive resin layer.
[0029] [6] The transfer film according to any one of [1] to [5], wherein the photosensitive resin layer contains a binder polymer, a polymerizable monomer, and a photopolymerization initiator.
[0030] [7] The transfer film according to [6], wherein the binder polymer has an acid value of 30 to 160 mgKOH / g.
[0031] [8] The transfer film according to [6] or [7], wherein the photosensitive resin layer further contains a compound that generates a group reactive with an acid group or a hydroxyl group when heated.
[0032] [9] The transfer film according to any one of [6] to [8], wherein the photosensitive resin layer further contains a compound capable of undergoing a Michael addition reaction.
[0033]
[10] The transfer film according to any one of [1] to [9], further comprising a refractive index adjusting layer having a higher refractive index than the photosensitive resin layer between the photosensitive resin layer and the protective film.
[0034]
[11] The transfer film according to any one of [1] to
[10] , which is used for forming an electrode protective film.
[0035]
[12] A method for producing a laminate, comprising: a first peeling step of peeling off the protective film from the transfer film described in any one of [1] to
[11] ;
[0036] A transfer step of transferring the transfer film after peeling off the protective film from the photosensitive resin layer side to the substrate having the electrode;
[0037] a curing step of curing at least a portion of the transferred photosensitive resin layer to form a cured film; and
[0038] In the second peeling step, after the curing step, the temporary support is peeled off to obtain a laminated body in which the cured film is laminated on the substrate having the electrode.
[0039]
[13] A method for manufacturing a touch panel, comprising: a first peeling step of peeling off the protective film from the transfer film described in any one of [1] to
[11] ;
[0040] a transfer step of transferring the transfer film after the protective film is peeled off from the photosensitive resin layer side to a touch panel substrate having a structure in which at least one of a touch panel electrode and a touch panel wiring is arranged on the substrate;
[0041] An exposure process of exposing the transferred photosensitive resin layer to a pattern;
[0042] a second peeling step of peeling off the temporary support after the exposure step; and
[0043] The developing step is to develop the pattern-exposed photosensitive resin layer after the second peeling step, thereby obtaining a touch panel protective film that protects at least a portion of at least one of the touch panel electrodes and the touch panel wirings.
[0044] Effects of the Invention
[0045] According to the present invention, it is possible to provide a transfer film, a method for producing a laminate, and a method for producing a touch panel, which have excellent releasability of a temporary support and a protective film and excellent punching workability of a cured film obtained by curing a transferred photosensitive resin layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a schematic cross-sectional view showing an example of the transfer film of the present invention.
[0047] Figure 2 This is a schematic cross-sectional view showing a first specific example of a touch panel having a photosensitive resin layer transferred using the transfer film of the present invention.
[0048] Figure 3This is a schematic cross-sectional view showing a second specific example of a touch panel having a photosensitive resin layer transferred using the transfer film of the present invention.
[0049] Figure 4 is a schematic diagram of a sample used to measure elongation at break. DETAILED DESCRIPTION
[0050] The content of the present invention will be described in detail below. The description of the constituent elements described below may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments.
[0051] In addition, in the present invention, "to" indicating a numerical range is used to mean that the numerical values described before and after it are included as the lower limit and the upper limit.
[0052] In the numerical ranges recorded in stages in this specification, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical ranges recorded in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiments.
[0053] Furthermore, in the notation of groups (atomic groups) in the present invention, the notation not indicating substituted or unsubstituted includes groups without substitution and groups with substitution. For example, "alkyl" means not only alkyl groups without substitution (unsubstituted alkyl groups) but also alkyl groups with substitution (substituted alkyl groups).
[0054] In the present invention, "mass %" and "weight %" have the same meaning, and "parts by mass" and "parts by weight" have the same meaning.
[0055] In addition, in the present invention, a combination of two or more preferred aspects is a more preferred aspect.
[0056] In the present invention, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition refers to the total amount of the plurality of substances present in the composition unless otherwise specified.
[0057] In the present invention, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0058] In the present invention, “(meth)acrylic acid” is a concept including both acrylic acid and methacrylic acid, “(meth)acrylate” is a concept including both acrylate and methacrylate, and “(meth)acryloyl” is a concept including both acryloyl and methacryloyl.
[0059] In addition, unless otherwise specified, the weight average molecular weight (Mw) and number average molecular weight (Mn) in the present invention are molecular weights converted using polystyrene as a standard substance by using a gel permeation chromatography (GPC) analysis apparatus using a column of TSKgel GMHxL, TSKgel G4000HxL, or TSKgel G2000HxL (all trade names manufactured by TOSOH CORPORATION), detecting using a solvent of THF (tetrahydrofuran) and a differential refractometer.
[0060] In the present invention, unless otherwise specified, the molecular weight of a compound having a molecular weight distribution is a weight average molecular weight.
[0061] In the present invention, unless otherwise specified, the ratio of the structural units of the polymer is a molar ratio.
[0062] In the present invention, unless otherwise specified, the refractive index is a value measured at a wavelength of 550 nm at 25° C. using an ellipsometer.
[0063] Hereinafter, the present invention will be described in detail.
[0064] [Transfer film]
[0065] The transfer film of the present invention is a transfer film including a temporary support, a photosensitive resin layer, and a protective film in this order.
[0066] Furthermore, in the transfer film of the present invention, the elongation at break of a cured film formed by curing the photosensitive resin layer at 120° C. is 15% or more.
[0067] In the transfer film of the present invention, the surface of the temporary support on the photosensitive resin layer side has an arithmetic mean roughness Ra of 50 nm or less, and the surface of the protective film on the photosensitive resin layer side has an arithmetic mean roughness Ra of 150 nm or less.
[0068] In the present invention, as described above, with respect to a transfer film having, in sequence, a temporary support having a surface with an arithmetic mean roughness Ra of less than 50 nm on the photosensitive resin layer side, a photosensitive resin layer having a breaking elongation of more than 15% at 120° C. after curing, and a protective film having a surface with an arithmetic mean roughness Ra of less than 150 nm on the photosensitive resin layer side, the temporary support and the protective film have excellent removability, and the stamping processability of the cured film formed by curing the transferred photosensitive resin layer is also improved.
[0069] Although the details are not clear, the present inventors speculate as follows.
[0070] That is, it is considered that the transfer film of the present invention has a photosensitive resin layer having a breaking elongation of 15% or more at 120° C. after curing, so that toughness is generated in the cured film formed by curing the transferred photosensitive resin layer, resulting in improved punching workability.
[0071] Furthermore, it is believed that the arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of the temporary support and the protective film is adjusted to the above-mentioned range based on the timing of peeling off the temporary support and the protective film and the timing of curing the transferred photosensitive resin layer, thereby maintaining good stamping processability and improving peelability.
[0072] Hereinafter, each layer of the transfer film of the present invention will be described in detail.
[0073] Temporary support
[0074] The transfer film of the present invention has a temporary support.
[0075] The temporary support is preferably a film, more preferably a resin film. As the temporary support, a flexible film that does not significantly deform, shrink, or stretch under pressure or under pressure and heating can be used.
[0076] Examples of such a film include a polyethylene terephthalate film (for example, a biaxially stretched polyethylene terephthalate film), a triacetyl cellulose film, a polystyrene film, a polyimide film, and a polycarbonate film.
[0077] Among them, a biaxially stretched polyethylene terephthalate film is particularly preferred as the temporary support.
[0078] Furthermore, it is preferred that the film used as the temporary support body has no deformation such as wrinkles or scratches.
[0079] From the viewpoint of enabling pattern exposure via the temporary support, the temporary support preferably has high transparency, and the transmittance at 365 nm is preferably 60% or more, more preferably 70% or more.
[0080] From the viewpoint of pattern formation during pattern exposure via a temporary support and transparency of the temporary support, the temporary support preferably has a small haze. Specifically, the temporary support preferably has a haze value of 2% or less, more preferably 0.5% or less, and particularly preferably 0.1% or less.
[0081] From the viewpoint of pattern formation when pattern exposure is performed via a temporary support and the transparency of the temporary support, it is preferred that the number of particles, foreign matter or defects contained in the temporary support is small. The number of particles, foreign matter or defects with a diameter of 1 μm or more is preferably 50 / 10 mm. 2 Below, more preferably 10 / 10mm2 Below, more preferably 3 / 10mm 2 Below, especially preferably 0 / 10mm 2 .
[0082] The temporary support included in the transfer film of the present invention has an arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of 50 nm or less, preferably 1 to 20 nm, and more preferably 1 to 12 nm.
[0083] Here, the arithmetic mean roughness Ra is the arithmetic mean roughness measured using an optical surface property measuring instrument in accordance with JIS B0601:2001.
[0084] In the present invention, from the viewpoint of adjusting the arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of the temporary support to the above range, the temporary support may not contain particles, and the layer structure contained in the temporary support may have a particle-containing layer constituting the surface on the photosensitive resin layer side.
[0085] The particles contained in the temporary support (particularly the particle-containing layer) may be organic particles or inorganic particles.
[0086] Specific examples of the organic particles include polyimide resins, olefin or modified olefin resins, crosslinked polystyrene resins, and silicone resins.
[0087] Specific examples of the inorganic particles include silicon oxide, calcium carbonate, agglomerated alumina, aluminum silicate, mica, clay, talc, and barium sulfate.
[0088] Furthermore, by adjusting the number or particle diameter of particles contained in the temporary support, the arithmetic mean roughness Ra of the surface of the temporary support on the photosensitive resin layer side can be adjusted to the above range.
[0089] The thickness of the temporary support is not particularly limited, but is preferably 5 μm to 200 μm, more preferably 10 μm to 150 μm, and even more preferably 10 μm to 50 μm from the viewpoint of ease of handling and versatility.
[0090] Preferred methods of temporary support bodies are described, for example, in paragraphs 0017 to 0018 of Japanese Patent Publication No. 2014-85643), paragraphs 0019 to 0026 of Japanese Patent Publication No. 2016-27363, paragraphs 0041 to 0057 of WO2012 / 081680A1, and paragraphs 0029 to 0040 of WO2018 / 179370A1. The contents of these publications may be incorporated into this specification.
[0091] Preferred commercial products of the temporary support include Lumirror 16KS40, Lumirror 16FB40 (manufactured by Toray Industries, Inc.), COSMOSHINE A4100, COSMOSHINE A4300, and COSMOSHINE A8300 (manufactured by TOYOB0 Co., Ltd.).
[0092] [Photosensitive resin layer]
[0093] The transfer film of the present invention has a photosensitive resin layer.
[0094] The photosensitive resin layer of the transfer film of the present invention is a photosensitive resin layer having a cured film having a breaking elongation of 15% or more at 120° C. In other words, the photosensitive resin layer has a property of having a breaking elongation of 15% or more at 120° C. after curing.
[0095] Here, regarding the elongation at break of the cured film at 120° C., a value measured by the method shown below is adopted.
[0096] First, the solid content concentration of the material for forming a photosensitive resin layer (hereinafter also referred to as "photosensitive resin composition") was appropriately adjusted, applied on Cerapeel (manufactured by Toray Industries, Inc.) so that the thickness after drying was 20 μm, and dried to form a coating film for evaluating the elongation at break.
[0097] Next, the coating film formed on the surface of Cerapeel was heated by ultra-high pressure mercury lamp at 120 mJ / cm 2 After exposure and curing, a high pressure mercury lamp was used at 400 mJ / cm 2 After additional exposure was performed and heating was performed at 145° C. for 30 minutes, the film was cut into a size of 3 cm×5 mm.
[0098] Thereafter, the coating film was peeled off from the Cerapeel.
[0099] The obtained coating film was subjected to a tensile test at a speed of 50 mm / min in an environment of 120° C. using a tensile tester (TENSILON RTG-1210: manufactured by A&D Company, Limited). Figure 4 As shown, the sample 1 is set on the chuck part 2 so that the measurement length becomes 20 mm. In addition, the sample width is 5 mm.
[0100] In this tensile test, the elongation at the point where the coating film broke was measured five times, and the average value was calculated as the elongation at break.
[0101] In the present invention, the elongation at break of the cured film formed by curing the transferred photosensitive resin layer is preferably at least twice as large as the elongation at break of the cured film formed by curing the photosensitive resin layer at 23°C because the punching processability of the cured film is further improved.
[0102] Here, regarding the elongation at break of the cured film at 23° C., a value measured by the same method as described above was adopted except that the environment of the tensile test was changed from 120° C. to 23° C.
[0103] In the present invention, the following formula (1) is preferably satisfied because the releasability of the temporary support and the protective film and the punching workability of the cured film formed by curing the transferred photosensitive resin layer can be achieved at a higher level.
[0104] X×Y<750 Formula (1)
[0105] Here, in formula (1), X represents the breaking elongation value (%) at 120° C. of a cured film obtained by curing the photosensitive resin layer, and Y represents the arithmetic mean roughness Ra value (nm) of the surface of the temporary support on the photosensitive resin layer side.
[0106] In the present invention, the value of X×Y is more preferably less than 400 and more than 70 because both the releasability of the temporary support and the protective film and the punching workability of the cured film formed by curing the transferred photosensitive resin layer can be further improved.
[0107] In the present invention, when used as an electrode protective film, the moisture permeability of the cured film formed by curing the photosensitive resin layer at a film thickness of 40 μm is preferably 500 g / m 2 / 24hr or less, more preferably 10 to 400 g / m 2 / 24hr, more preferably 10 to 300 g / m 2 / 24hr.
[0108] Here, the water vapor permeability of the cured film at a film thickness of 40 μm is measured in the following procedure.
[0109] <Preparation of Sample for Moisture Permeability Measurement>
[0110] The photosensitive resin composition was applied onto a polyethylene terephthalate (PET) film having a thickness of 75 μm as a temporary support using a slit nozzle and then dried to form a photosensitive resin layer having a thickness of 8 μm, thereby obtaining a transfer film for sample preparation.
[0111] Next, the transfer film for sample preparation was laminated on a PTFE (tetrafluoroethylene resin) membrane filter FP-100-100 manufactured by Sumitomo Electric Industries, Ltd. to form a laminate A having a layer structure of temporary support / photosensitive resin layer with a thickness of 8 μm / membrane filter. The lamination conditions were set to a membrane filter temperature of 40° C., a pressure roller temperature of 110° C., a linear pressure of 3 N / cm, and a conveying speed of 2 m / min.
[0112] Next, the temporary support is peeled off from the laminate A.
[0113] By repeating this operation five or more times, a laminate B having a laminate structure of photosensitive resin layer / membrane filter with a total film thickness of 40 μm was formed.
[0114] Using i-ray with exposure of 300mJ / cm 2 After the photosensitive resin layer of the obtained laminated body B was exposed, post-baking was performed at 145° C. for 30 minutes to cure the photosensitive resin layer to form a cured film.
[0115] As described above, a sample for measuring moisture permeability having a laminated structure of a cured film / membrane filter with a total film thickness of 40 μm was obtained.
[0116] <Measurement of moisture permeability>
[0117] Using a sample for measuring water vapor permeability, water vapor permeability measurement was performed by a cup method with reference to JIS-Z-0208 (1976).
[0118] First, a circular sample having a diameter of 70 mm is cut out from the sample for measuring the moisture permeability.
[0119] Next, 20 g of dried calcium chloride was placed in the measuring cup, and then the measuring cup was covered with the circular sample to prepare a measuring cup with a lid.
[0120] The measuring cup with the lid was left to stand in a constant temperature and humidity chamber at 65° C. and 90% relative humidity (RH) for 24 hours.
[0121] The water vapor permeability of the circular sample (unit: g / m 2 / 24hr).
[0122] The above measurement was performed three times, and the average value of the water vapor permeability was calculated as the moisture permeability.
[0123] The photosensitive resin layer of the transfer film of the present invention preferably contains a binder polymer, a polymerizable monomer, and a photopolymerization initiator, and is more preferably formed using a photosensitive resin composition containing a binder polymer, a polymerizable monomer, and a photopolymerization initiator.
[0124] <Binder Polymer>
[0125] The binder polymer is preferably an alkali-soluble resin.
[0126] For example, from the viewpoint of developability, the binder polymer preferably has an acid value of 30 to 160 mgKOH / g, and more preferably is an alkali-soluble resin having an acid value of 30 to 160 mgKOH / g.
[0127] In the present invention, "alkali-soluble" means that the solubility of sodium carbonate in a 1% by mass aqueous solution at 22°C is 0.1% by mass or more.
[0128] The acid value of the binder polymer is a value measured according to the method described in JIS K0070:1992.
[0129] Furthermore, for example, from the viewpoint of easily forming a strong film by thermal cross-linking with the cross-linking component by heating, the binder polymer is further preferably a resin having a carboxyl group with an acid value of 30 to 160 mgKOH / g (so-called carboxyl-containing resin), and particularly preferably an acrylic resin having a carboxyl group with an acid value of 30 to 160 mgKOH / g (so-called carboxyl-containing acrylic resin).
[0130] In the present invention, acrylic resin refers to a resin having a structural unit derived from a (meth)acrylic compound, and the content of the structural unit is preferably 30% by mass or more, more preferably 50% by mass or more, based on the total mass of the resin.
[0131] From the viewpoints of the moisture permeability and flexural resistance of the obtained cured film and the adhesiveness of the obtained uncured film, the binder polymer is preferably an acrylic resin or a styrene-acrylic acid copolymer, and more preferably a styrene-acrylic acid copolymer.
[0132] In the present invention, the styrene-acrylic acid copolymer refers to a resin having a structural unit derived from a styrene compound and a structural unit derived from a (meth)acrylic acid compound, and the total content of the structural unit derived from the styrene compound and the structural unit derived from the (meth)acrylic acid compound is preferably 30% by mass or more, more preferably 50% by mass or more, relative to the total mass of the above-mentioned copolymer.
[0133] Furthermore, the content of the structural unit derived from the styrene compound is preferably 1% by mass or more, more preferably 5% by mass or more, and particularly preferably 5% by mass or more and 80% by mass or less, based on the total mass of the copolymer.
[0134] The content of the structural unit derived from the (meth)acrylic acid compound is preferably 5% by mass or more, more preferably 10% by mass or more, and particularly preferably 20% by mass or more and 95% by mass or less, based on the total mass of the copolymer.
[0135] Examples of the (meth)acrylic compound include (meth)acrylate compounds, (meth)acrylic acid, (meth)acrylamide compounds, (meth)acrylonitrile, etc. Among them, at least one compound selected from the group consisting of (meth)acrylate compounds and (meth)acrylic acid is also preferred.
[0136] -Structural unit having an aromatic ring-
[0137] From the viewpoint of the moisture permeability and strength of the obtained cured film, the binder polymer preferably contains a structural unit having an aromatic ring.
[0138] Examples of the monomer that forms the structural unit having an aromatic ring include styrene, tert-butoxystyrene, methylstyrene, α-methylstyrene, and benzyl (meth)acrylate.
[0139] Among them, styrene compounds are preferred, and styrene is particularly preferred.
[0140] Furthermore, from the viewpoint of the moisture permeability and strength of the obtained cured film, the binder polymer more preferably has a structural unit represented by the following formula (S) (structural unit derived from styrene).
[0141] [Chemical formula 1]
[0142]
[0143] When the binder polymer contains a structural unit having an aromatic ring, the content of the structural unit having an aromatic ring is preferably 5% by mass to 90% by mass, more preferably 10% by mass to 70% by mass, and particularly preferably 20% by mass to 50% by mass, relative to the total mass of the binder polymer, from the viewpoint of moisture permeability and strength of the obtained cured film.
[0144] Furthermore, from the viewpoint of moisture permeability and strength of the obtained cured film, the content of the structural unit having an aromatic ring in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and particularly preferably 20 mol % to 50 mol %, relative to the total amount of the binder polymer.
[0145] In addition, from the viewpoint of moisture permeability and strength of the obtained cured film, the content of the structural unit represented by the above formula (S) in the binder polymer is preferably 5 mol% to 70 mol%, more preferably 10 mol% to 60 mol%, and particularly preferably 20 mol% to 50 mol%, relative to the total amount of the binder polymer.
[0146] In addition, in the present invention, when the content of "structural unit" is specified by molar ratio, the meaning of the above "structural unit" is the same as the meaning of "monomer unit". In addition, in the present invention, the above "monomer unit" may be modified after polymerization by polymer reaction or the like. The same applies to the following.
[0147] -Structural unit having an aliphatic hydrocarbon ring-
[0148] From the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film, the binder polymer preferably contains a structural unit having an aliphatic hydrocarbon ring.
[0149] Examples of the aliphatic hydrocarbon ring in the structural unit having an aliphatic hydrocarbon ring include a tricyclodecane ring, a cyclohexane ring, a cyclopentane ring, a norbornane ring, and an isobornane ring.
[0150] Among these, from the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film, a ring formed by condensing two or more aliphatic hydrocarbon rings is preferred, and a tetrahydrodicyclopentadiene ring (tricyclo[5.2.1.0 2,6 ]decane ring).
[0151] Examples of the monomer that forms the structural unit having an aliphatic hydrocarbon ring include dicyclopentanyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate.
[0152] Furthermore, from the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film, the binder polymer more preferably has a structural unit represented by the following formula (Cy), and particularly preferably has a structural unit represented by the above formula (S) and a structural unit represented by the following formula (Cy).
[0153] [Chemical formula 2]
[0154]
[0155] In formula (Cy), R M represents a hydrogen atom or a methyl group, R Cy It represents a monovalent group having an aliphatic hydrocarbon ring structure.
[0156] R in formula (Cy) M Preferred is methyl.
[0157] From the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film, R in the formula (Cy) is Cy It is preferably a monovalent group having an aliphatic hydrocarbon ring structure having 5 to 20 carbon atoms, more preferably a monovalent group having an aliphatic hydrocarbon ring structure having 6 to 16 carbon atoms, and particularly preferably a monovalent group having an aliphatic hydrocarbon ring structure having 8 to 14 carbon atoms.
[0158] Furthermore, from the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film, R in the formula (Cy) is Cy The aliphatic hydrocarbon ring structure in is preferably a cyclopentane ring structure, a cyclohexane ring structure, a tetrahydrodicyclopentadiene ring structure, a norbornane ring, or an isobornane ring, more preferably a cyclohexane ring structure or a tetrahydrodicyclopentadiene ring structure, and particularly preferably a tetrahydrodicyclopentadiene ring structure.
[0159] In addition, from the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film, R in the formula (Cy) is Cy The aliphatic hydrocarbon ring structure in is preferably a ring structure in which two or more aliphatic hydrocarbon rings are condensed, and more preferably a ring in which two or more and four or less aliphatic hydrocarbon rings are condensed.
[0160] In addition, from the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film, R in the formula (Cy) is preferably Cy Preferred is a group in which the oxygen atom of -C(=O)O- in the formula (Cy) is directly bonded to the aliphatic hydrocarbon ring structure, that is, an aliphatic hydrocarbon ring group, more preferably a cyclohexyl group or a dicyclopentyl group, and particularly preferably a dicyclopentyl group.
[0161] The binder polymer may have one type of structural unit having an aliphatic hydrocarbon ring alone, or may have two or more types.
[0162] When the binder polymer contains a structural unit having an aliphatic hydrocarbon ring, the content of the structural unit having an aliphatic hydrocarbon ring is preferably 5% by mass to 90% by mass, more preferably 10% by mass to 80% by mass, and particularly preferably 20% by mass to 70% by mass, relative to the total mass of the binder polymer, from the viewpoint of moisture permeability and strength of the obtained cured film.
[0163] Furthermore, from the viewpoint of moisture permeability and strength of the obtained cured film, the content of the structural unit having an aliphatic hydrocarbon ring in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and particularly preferably 20 mol % to 50 mol %, relative to the total amount of the binder polymer.
[0164] In addition, from the viewpoint of moisture permeability and strength of the obtained cured film, the content of the structural unit represented by the above formula (Cy) in the binder polymer is preferably 5 mol% to 70 mol%, more preferably 10 mol% to 60 mol%, and particularly preferably 20 mol% to 50 mol%, relative to the total amount of the binder polymer.
[0165] When the binder polymer contains a structural unit having an aromatic ring and a structural unit having an aliphatic hydrocarbon ring, the total content of the structural unit having an aromatic ring and the structural unit having an aliphatic hydrocarbon ring is preferably 10% by mass to 90% by mass, more preferably 20% by mass to 80% by mass, and particularly preferably 40% by mass to 75% by mass, relative to the total mass of the binder polymer, from the viewpoint of moisture permeability, flex resistance and strength of the obtained cured film.
[0166] Furthermore, from the viewpoint of moisture permeability, bending resistance and strength of the obtained cured film, the total content of structural units having aromatic rings and structural units having aliphatic hydrocarbon rings in the binder polymer is preferably 10 mol % to 80 mol %, more preferably 20 mol % to 70 mol %, and particularly preferably 40 mol % to 60 mol %, relative to the total amount of the binder polymer.
[0167] Furthermore, from the viewpoint of moisture permeability, bending resistance and strength of the obtained cured film, the total content of the structural unit represented by the above formula (S) and the structural unit represented by the above formula (Cy) in the binder polymer is preferably 10 mol% to 80 mol%, more preferably 20 mol% to 70 mol%, and particularly preferably 40 mol% to 60 mol%, relative to the total amount of the binder polymer.
[0168] Furthermore, from the viewpoint of moisture permeability, bending resistance and strength of the obtained cured film, the molar amount nS of the structural unit represented by the above formula (S) and the molar amount nCy of the structural unit represented by the above formula (Cy) in the binder polymer preferably satisfy the relationship shown by the following formula (SCy), more preferably satisfy the following formula (SCy-1), and particularly preferably satisfy the following formula (SCy-2).
[0169] 0.2≤nS / (nS+nCy)≤0.8 Formula (SCy)
[0170] 0.30≤nS / (nS+nCy)≤0.75 Formula (SCy-1)
[0171] 0.40≤nS / (nS+nCy)≤0.70 Formula (SCy-2)
[0172] -Structural unit having an acid group-
[0173] From the viewpoint of the strength and developability of the obtained cured film, the binder polymer preferably contains a structural unit having an acid group.
[0174] Examples of the acid group include a carboxyl group, a sulfonic acid group, a phosphonic acid group, and a phosphoric acid group, and a carboxyl group is preferred.
[0175] As the structural unit having the acid group, preferably, a structural unit derived from (meth)acrylic acid as shown below is used, and more preferably, a structural unit derived from methacrylic acid is used.
[0176] [Chemical formula 3]
[0177]
[0178] The binder polymer may have one type of structural unit having an acid group alone, or may have two or more types.
[0179] When the binder polymer contains a structural unit having an acid group, the content of the structural unit having an acid group is preferably 5% by mass to 50% by mass, more preferably 5% by mass to 40% by mass, and particularly preferably 10% by mass to 30% by mass, relative to the total mass of the binder polymer, from the viewpoint of the strength and developability of the obtained cured film.
[0180] Furthermore, from the viewpoint of the strength and developability of the obtained cured film, the content of the structural unit having an acid group in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 50 mol %, and particularly preferably 20 mol % to 40 mol %, relative to the total amount of the binder polymer.
[0181] Furthermore, from the viewpoint of the strength and developability of the obtained cured film, the content of the structural unit derived from (meth)acrylic acid in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 50 mol %, and particularly preferably 20 mol % to 40 mol %, relative to the total amount of the binder polymer.
[0182] -Constituent unit having a reactive group-
[0183] From the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film, the binder polymer preferably has a reactive group, and more preferably contains a structural unit having a reactive group.
[0184] As the reactive group, a radical polymerizable group is preferred, and an ethylenically unsaturated group is more preferred. Furthermore, when the binder polymer has an ethylenically unsaturated group, the binder polymer preferably contains a structural unit having an ethylenically unsaturated group in a side chain.
[0185] In the present invention, the "main chain" means the relatively longest bond chain in the molecule of the polymer compound constituting the resin, and the "side chain" means an atomic group branched from the main chain.
[0186] The ethylenically unsaturated group is preferably a (meth)acrylic group, and more preferably a (meth)acryloyloxy group.
[0187] Examples of the structural unit having a reactive group include the structural units shown below, but are of course not limited to these.
[0188] [Chemical formula 4]
[0189]
[0190] The binder polymer may have one type of structural unit having a reactive group alone, or may have two or more types.
[0191] In the case where the binder polymer contains a structural unit having a reactive group, from the viewpoint of the strength of the obtained cured film and the adhesion of the obtained uncured film, the content of the structural unit having the reactive group is preferably 5% by mass to 70% by mass, more preferably 10% by mass to 50% by mass, and particularly preferably 20% by mass to 40% by mass, relative to the total mass of the binder polymer.
[0192] Furthermore, from the viewpoint of the strength of the obtained cured film and the adhesion of the obtained uncured film, the content of the structural unit having a reactive group in the binder polymer is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and particularly preferably 20 mol % to 50 mol %, relative to the total amount of the binder polymer.
[0193] Examples of methods for introducing reactive groups into binder polymers include methods of reacting epoxy compounds, blocked isocyanate compounds, isocyanate compounds, vinyl sulfone compounds, aldehyde compounds, methylol compounds, carboxylic anhydride, etc. with hydroxyl groups, carboxyl groups, primary amino groups, secondary amino groups, acetoacetyl groups, sulfonic acids, etc.
[0194] As a preferred example of a method for introducing a reactive group into a binder polymer, there is a method in which a polymer having a carboxyl group is synthesized by polymerization reaction, and then glycidyl (meth)acrylate is reacted with a part of the carboxyl groups of the obtained polymer by polymer reaction to introduce a (meth)acryloyloxy group into the polymer. By this method, a binder polymer having a (meth)acryloyloxy group on a side chain can be obtained.
[0195] The above-mentioned polymerization reaction is preferably carried out at a temperature of 70°C to 100°C, and more preferably at a temperature of 80°C to 90°C. As the polymerization initiator used in the above-mentioned polymerization reaction, an azo initiator is preferred, and for example, V-601 (trade name) or V-65 (trade name) manufactured by FUJIFILM Wako Pure Chemical Corporation is more preferred. The above-mentioned polymer reaction is preferably carried out at a temperature of 80°C to 110°C. In the above-mentioned polymer reaction, a catalyst such as an ammonium salt is preferably used.
[0196] From the perspective of patterning and reliability, the content of residual monomers in each structural unit of the binder polymer is preferably 5,000 mass ppm or less, more preferably 2,000 mass ppm or less, and further preferably 500 mass ppm or less relative to the total mass of the binder polymer. The lower limit is not particularly limited, but is preferably 1 mass ppm or more, and more preferably 10 mass ppm or more.
[0197] From the perspective of patterning and reliability, the residual monomer of each structural unit of the binder polymer is preferably 3,000 mass ppm or less, more preferably 600 mass ppm or less, and further preferably 100 mass ppm or less relative to the total mass of the photosensitive composition described later. The lower limit is not particularly limited, but is preferably 0.1 mass ppm or more, and more preferably 1 mass ppm or more.
[0198] The residual monomer amount of monomers when synthesizing the binder polymer by polymer reaction is also preferably within the above range. For example, when synthesizing the binder polymer by reacting glycidyl acrylate with a carboxylic acid side chain, the content of glycidyl acrylate is preferably within the above range.
[0199] The amount of residual monomers can be measured by a known method such as liquid chromatography analysis, gas chromatography analysis, etc.
[0200] Preferred examples of the binder polymer include the following polymers: The content ratio (a to d) and weight average molecular weight Mw of each structural unit shown below can be appropriately changed depending on the purpose.
[0201] [Chemical formula 5]
[0202]
[0203] [Chemical formula 6]
[0204]
[0205] From the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film, the weight average molecular weight (Mw) of the binder polymer is preferably 5,000 or more, more preferably 10,000 or more, further preferably 10,000 to 50,000, and particularly preferably 20,000 to 30,000.
[0206] The photosensitive resin layer or the photosensitive resin composition may contain only one type of binder polymer, or may contain two or more types.
[0207] For example, from the viewpoint of the strength of the cured film and the operability in the transfer film, the content of the binder polymer is preferably 10% to 90% by mass, more preferably 20% to 80% by mass, and further preferably 30% to 70% by mass, relative to the total solid content of the photosensitive resin layer or the photosensitive resin composition.
[0208] <Polymerizable Monomer>
[0209] As the polymerizable monomer, a radical polymerizable compound having an ethylenically unsaturated group (hereinafter also simply referred to as an "ethylenically unsaturated compound") is preferred.
[0210] The radical polymerizable compound having an ethylenically unsaturated group is a component that contributes to the photosensitivity (ie, photocurability) of the photosensitive resin layer and the strength of the cured film.
[0211] Furthermore, the ethylenically unsaturated compound is a compound having one or more ethylenically unsaturated groups.
[0212] As the ethylenically unsaturated compound, the photosensitive resin layer preferably contains a bifunctional or higher-functional ethylenically unsaturated compound.
[0213] Here, the bifunctional or higher-functional ethylenically unsaturated compound refers to a compound having two or more ethylenically unsaturated groups in one molecule.
[0214] As the ethylenically unsaturated group, a (meth)acryloyl group is more preferred.
[0215] As the ethylenically unsaturated compound, a (meth)acrylate compound is preferred.
[0216] In view of curability after curing, the photosensitive resin layer particularly preferably contains a bifunctional ethylenically unsaturated compound (preferably a bifunctional (meth)acrylate compound) or a trifunctional or higher ethylenically unsaturated compound (preferably a trifunctional or higher (meth)acrylate compound).
[0217] The bifunctional ethylenically unsaturated compound is not particularly limited, and can be appropriately selected from known compounds.
[0218] Examples of the bifunctional ethylenically unsaturated compound include tricyclodecane dimethanol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate.
[0219] More specifically, bifunctional ethylenically unsaturated compounds include tricyclodecane dimethanol diacrylate (A-DCP, manufactured by Shin Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol dimethacrylate (DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (A-NOD-N, manufactured by Shin Nakamura Chemical Co., Ltd.), and 1,6-hexanediol diacrylate (A-HD-N, manufactured by Shin Nakamura Chemical Co., Ltd.).
[0220] The trifunctional or higher-functional ethylenically unsaturated compound is not particularly limited and can be appropriately selected from known compounds.
[0221] Examples of trifunctional or higher-functional ethylenically unsaturated compounds include dipentaerythritol (tri / tetra / penta / hexa) (meth)acrylate, pentaerythritol (tri / tetra) (meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, isocyanuric acid (meth)acrylate, and (meth)acrylate compounds having a glycerol tri(meth)acrylate skeleton.
[0222] Here, “(tri / tetra / penta / hexa) (meth)acrylate” is a concept including tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate and hexa(meth)acrylate, and “(tri / tetra) (meth)acrylate” is a concept including tri(meth)acrylate and tetra(meth)acrylate.
[0223] Examples of the ethylenically unsaturated compound include caprolactone-modified compounds of (meth)acrylate compounds (KAYARAD (registered trademark) DPCA-20 manufactured by Nippon Kayaku Co., Ltd., A-9300-1CL manufactured by Shin Nakamura Chemical Co., Ltd., etc.), alkylene oxide-modified compounds of (meth)acrylate compounds (KAYARAD RP-1040 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by Shin Nakamura Chemical Co., Ltd., EBECRYL (registered trademark) 135 manufactured by DAICEL-ALLNEX LTD., etc.), and ethoxylated glyceryl triacrylate (A-GLY-9E manufactured by Shin Nakamura Chemical Co., Ltd., etc.).
[0224] As the ethylenically unsaturated compound, a urethane (meth)acrylate compound (preferably a trifunctional or higher-functional urethane (meth)acrylate compound) can also be mentioned. The upper limit of the number of functional groups can be, for example, 20 or less.
[0225] Examples of trifunctional or higher-functional urethane (meth)acrylate compounds include 8UX-015A (manufactured by TAISEIFINE CHEMICAL CO., LTD.), UA-32P (manufactured by Shin-Nakamura Chemical Co., Ltd.), UA-1100H (manufactured by Shin-Nakamura Chemical Co., Ltd.), AH-600 (trade name) manufactured by KYOEISHA CHEMICAL CO., LTD., UA-306H, UA-306T, UA-306I, UA-510H, and UX-5000 (manufactured by Nippon Kayaku Co., Ltd.).
[0226] Furthermore, from the viewpoint of improving developability, the ethylenically unsaturated compound preferably contains an ethylenically unsaturated compound having an acid group.
[0227] Examples of the acid group include a phosphoric acid group, a sulfonic acid group, and a carboxyl group, and a carboxyl group is preferred.
[0228] Examples of the ethylenically unsaturated compound having an acid group include tri- to tetra-functional ethylenically unsaturated compounds having an acid group (formed by introducing a carboxyl group into a pentaerythritol tri- and tetra-acrylate (PETA) skeleton (acid value = 80 to 120 mgKOH / g)), penta- to hexa-functional ethylenically unsaturated compounds having an acid group (formed by introducing a carboxyl group into a dipentaerythritol penta- and hexa-acrylate (DPHA) skeleton (acid value = 25 to 70 mgKOH / g)), etc. These tri- or higher-functional ethylenically unsaturated compounds having an acid group can be used together with a bi-functional ethylenically unsaturated compound having an acid group as required.
[0229] The ethylenically unsaturated compound having an acid group is preferably at least one selected from the group consisting of bifunctional or higher-functional ethylenically unsaturated compounds containing a carboxyl group and carboxylic acid anhydrides thereof. This improves developability and cured film strength.
[0230] The bifunctional or higher functional ethylenically unsaturated compound containing a carboxyl group is not particularly limited and can be appropriately selected from known compounds.
[0231] As the bifunctional or higher-functional ethylenically unsaturated compound containing a carboxyl group, for example, ARONIX (registered trademark) TO-2349 (manufactured by TOAGOSEI CO., LTD.), ARONIX M-520 (manufactured by TOAGOSEI CO., LTD.) or ARONIX M-510 (manufactured by TOAGOSEI CO., LTD.) can be preferably used.
[0232] The ethylenically unsaturated compound having an acid group is preferably a polymerizable compound having an acid group described in paragraphs 0025 to 0030 of JP-A-2004-239942, the contents of which are incorporated into the present specification.
[0233] In the present invention, the ethylenically unsaturated compound is preferably a compound A represented by the following formula (I) (also simply referred to as "compound A").
[0234] Q 2 -R 1 -Q 1 Formula (I)
[0235] In formula (I), Q 1 and Q 2 Each independently represents a (meth)acryloyloxy group, R 1 It represents a divalent linking group having a chain structure.
[0236] From the viewpoint of ease of synthesis, Q in formula (I) 1 and Q 2 Optimize Q 1 and Q 2are the same group.
[0237] Furthermore, from the viewpoint of reactivity, Q in formula (I) 1 and Q 2 An acryloyloxy group is preferred.
[0238] From the viewpoint of the bending resistance of the obtained cured film, R in the formula (I) 1 Preferably, alkylene, alkyleneoxyalkylene (-L 1 -OL 1 -), or polyalkyleneoxyalkylene (-(L 1 -O) p -L 1 -), more preferably a hydrocarbon group or polyalkyleneoxyalkylene group having 2 to 20 carbon atoms, further preferably an alkylene group having 4 to 20 carbon atoms, and particularly preferably a linear alkylene group having 6 to 18 carbon atoms. The hydrocarbon group may have a chain structure in at least a part thereof, and may be, for example, linear, branched, cyclic, or any combination thereof. From the viewpoint of the bending resistance of the cured film obtained, an alkylene group or a group combining two or more alkylene groups and one or more arylene groups is preferred, an alkylene group is more preferred, and a linear alkylene group is particularly preferred.
[0239] In addition, the above L 1 Each independently represents an alkylene group, and is preferably a vinyl group, a propylene group, or a butylene group, and more preferably a vinyl group or a 1,2-propylene group. p represents an integer of 2 or more, and is preferably an integer of 2 to 10.
[0240] Furthermore, from the viewpoint of moisture permeability and flexural resistance of the obtained cured film, the linking Q in compound A 1 and Q 2 The number of atoms in the shortest connecting chain between them is preferably 3 to 50, more preferably 4 to 40, further preferably 6 to 20, and particularly preferably 8 to 12.
[0241] In the present invention, "connect Q 1 and Q 2 The number of atoms in the shortest link between Q 1 R 1 The atoms in are connected to Q 2 R 1 The shortest atomic number of the atoms in the .
[0242] Specific examples of compound A include 1,3-butanediol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,4-cyclohexanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, di(meth)acrylate of hydrogenated bisphenol A, di(meth)acrylate of hydrogenated bisphenol F, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, poly(ethylene glycol / propylene glycol) di(meth)acrylate, and polybutylene glycol di(meth)acrylate. The above ester monomers may also be used as a mixture.
[0243] From the viewpoint of the bending resistance of the obtained cured film, among the above compounds, at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate and neopentyl glycol di(meth)acrylate is preferred, at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate and 1,10-decanediol di(meth)acrylate is more preferred, and at least one compound selected from the group consisting of 1,9-nonanediol di(meth)acrylate and 1,10-decanediol di(meth)acrylate is particularly preferred.
[0244] The weight average molecular weight (Mw) of the ethylenically unsaturated compound is preferably 200 to 3,000, more preferably 250 to 2,600, further preferably 280 to 2,200, and particularly preferably 300 to 2,200.
[0245] Furthermore, among the ethylenically unsaturated compounds used in the photosensitive resin layer, the proportion of the ethylenically unsaturated compounds having a molecular weight of 300 or less relative to all the ethylenically unsaturated compounds contained in the photosensitive resin layer is preferably 30% by mass or less, more preferably 25% by mass or less, and further preferably 20% by mass or less.
[0246] The ethylenically unsaturated compound may be used alone or in combination of two or more.
[0247] The content of the ethylenically unsaturated compound in the photosensitive resin layer is preferably 1% to 70% by mass, more preferably 5% to 70% by mass, further preferably 10% to 70% by mass, particularly preferably 20% to 60% by mass, and most preferably 20% to 50% by mass, relative to the total mass of the photosensitive resin layer.
[0248] Furthermore, when the photosensitive resin layer contains a difunctional ethylenically unsaturated compound and a trifunctional or higher-functional ethylenically unsaturated compound, the content of the difunctional ethylenically unsaturated compound is preferably 10% to 90% by mass, more preferably 20% to 85% by mass, and further preferably 30% to 80% by mass, relative to all the ethylenically unsaturated compounds contained in the photosensitive resin layer.
[0249] In this case, the content of the trifunctional or higher ethylenically unsaturated compound is preferably 10 to 90% by mass, more preferably 15 to 80% by mass, and further preferably 20 to 70% by mass based on all ethylenically unsaturated compounds contained in the photosensitive resin layer.
[0250] Furthermore, at this time, relative to the total content of the difunctional ethylenically unsaturated compound and the trifunctional or higher-functional ethylenically unsaturated compound, the content of the difunctional or higher-functional ethylenically unsaturated compound is preferably 40% by mass or more and less than 100% by mass, more preferably 40% by mass to 90% by mass, further preferably 50% by mass to 80% by mass, and particularly preferably 50% by mass to 70% by mass.
[0251] Furthermore, when the photosensitive resin layer contains a bifunctional or higher-functional ethylenically unsaturated compound, the photosensitive resin layer may further contain a monofunctional ethylenically unsaturated compound.
[0252] Furthermore, when the photosensitive resin layer contains a difunctional or higher-functional ethylenically unsaturated compound, it is preferred that the difunctional or higher-functional ethylenically unsaturated compound is a main component among the ethylenically unsaturated compounds contained in the photosensitive resin layer.
[0253] Specifically, when the photosensitive resin layer contains ethylenically unsaturated compounds having two or more functional groups, the content of the ethylenically unsaturated compounds having two or more functional groups is preferably 60% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass, relative to the total content of the ethylenically unsaturated compounds contained in the photosensitive resin layer.
[0254] Furthermore, when the photosensitive resin layer contains an ethylenically unsaturated compound having an acid group (preferably a bifunctional or higher-functional ethylenically unsaturated compound containing a carboxyl group or its carboxylic anhydride), the content of the ethylenically unsaturated compound having an acid group is preferably 1% by mass to 50% by mass, more preferably 1% by mass to 20% by mass, and further preferably 1% by mass to 10% by mass, relative to the photosensitive resin layer.
[0255] <Photopolymerization Initiator>
[0256] The photopolymerization initiator is not particularly limited, and a known photopolymerization initiator can be used.
[0257] Examples of the photopolymerization initiator include a photopolymerization initiator having an oxime ester structure (hereinafter also referred to as an "oxime-based photopolymerization initiator"), a photopolymerization initiator having an α-aminoalkylphenone structure (hereinafter also referred to as an "α-aminoalkylphenone-based photopolymerization initiator"), a photopolymerization initiator having an α-hydroxyalkylphenone structure (hereinafter also referred to as an "α-hydroxyalkylphenone-based photopolymerization initiator"), a photopolymerization initiator having an acylphosphine oxide structure (hereinafter also referred to as an "acylphosphine oxide-based photopolymerization initiator"), and a photopolymerization initiator having an N-phenylglycine structure (hereinafter also referred to as an "N-phenylglycine-based photopolymerization initiator"), etc.
[0258] The photopolymerization initiator preferably includes at least one selected from the group consisting of oxime-based photopolymerization initiators, α-aminoalkylphenone-based photopolymerization initiators, α-hydroxyalkylphenone-based photopolymerization initiators, and N-phenylglycine-based photopolymerization initiators, and more preferably includes at least one selected from the group consisting of oxime-based photopolymerization initiators, α-aminoalkylphenone-based photopolymerization initiators, and N-phenylglycine-based photopolymerization initiators.
[0259] Furthermore, as the photopolymerization initiator, for example, the polymerization initiators described in paragraphs 0031 to 0042 of JP-A-2011-95716 and paragraphs 0064 to 0081 of JP-A-2015-014783 may be used.
[0260] Examples of commercially available photopolymerization initiators include 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyl oxime) [trade name: IRGACURE (registered trademark) OXE-01, manufactured by BASF], 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyl oxime) [trade name: IRGACURE (registered trademark) OXE-02, manufactured by BASF], and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyl oxime) [trade name: IRGACURE (registered trademark) OXE-03, manufactured by BASF]. F Company], IRGACURE (registered trademark) OXE03 (manufactured by BASF), IRGACURE (registered trademark) OXE04 (manufactured by BASF), 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone [trade name: IRGACURE (registered trademark) 379EG, manufactured by BASF], 2-methyl-1-(4-methylthio phenyl)-2-morpholinopropan-1-one [trade name: IRGACURE (registered trademark) 907, manufactured by BASF], 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one [trade name: IRGACURE (registered trademark) 127, manufactured by BASF], 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1 [trade name: IRGACURE (registered trademark) 369, manufactured by BASF], 2-hydroxy-2-methyl-1-phenylpropan-1-one [trade name: IRGACURE (registered trademark) 1173, manufactured by BASF], 1-hydroxycyclohexylphenyl ketone [trade name: IRGACURE (registered trademark) 184, manufactured by BASF], 2,2-dimethoxy-1,2-diphenylethane-1-one [trade name: IRGACURE 651, BASF Corporation, etc., oxime ester series [trade name: Lunar (registered trademark) 6, DKSH Management Ltd.], 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(O-benzoyl oxime) (trade name: TR-PBG-305, manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furylcarbonyl)-9H-carbazole-3-yl]-2-(O-acetyl oxime) (trade name: TR-PBG-326, manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.), 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazole-3-yl)-propane-1,2-dione-2-(O-benzoyl oxime) (trade name: TR-PBG-391, manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.), etc.
[0261] The photosensitive resin layer or the photosensitive resin composition may contain only one type of photopolymerization initiator, or may contain two or more types.
[0262] The content of the photopolymerization initiator is not particularly limited, but is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1.0% by mass or more, based on the total solid content of the photosensitive resin layer or the photosensitive resin composition.
[0263] Furthermore, the content of the photopolymerization initiator is preferably 10% by mass or less, and more preferably 5% by mass or less, based on the total solid content of the photosensitive resin layer or the photosensitive resin composition.
[0264] Because the stamping processability of the cured film formed by the photosensitive resin layer after curing transfer becomes better, the photosensitive resin layer possessed by the transfer film of the present invention or the photosensitive resin composition forming the photosensitive resin layer preferably contains a compound that produces a group capable of reacting with an acid group or a hydroxyl group by heating (hereinafter also referred to as a "thermal cross-linking compound").
[0265] Examples of the heat-crosslinkable compound include epoxy compounds, oxetane compounds, methylol compounds, blocked isocyanate compounds, etc. Among them, the following blocked isocyanate compounds are preferred from the viewpoint of the strength of the obtained cured film and the adhesiveness of the obtained uncured film.
[0266] <Blocked isocyanate compound>
[0267] The blocked isocyanate compound refers to a "compound having a structure in which the isocyanate group of isocyanate is protected (so-called masked) by a blocking agent".
[0268] The dissociation temperature of the blocked isocyanate compound is not particularly limited, but is preferably 100°C to 160°C, more preferably 130°C to 150°C.
[0269] Here, the dissociation temperature of the blocked isocyanate refers to "the temperature of an endothermic peak accompanying the deprotection reaction of the blocked isocyanate when measured by DSC (Differential scanning calorimetry) analysis using a differential scanning calorimeter".
[0270] As the differential scanning calorimeter, for example, a differential scanning calorimeter (model: DSC6200) manufactured by Seiko Instruments Inc. can be preferably used. However, the differential scanning calorimeter is not limited to this.
[0271] As the end-capping agent having a dissociation temperature of 100°C to 160°C, there can be mentioned active methylene compounds [(malonic acid diesters (dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-2-ethylhexyl malonate, etc.)], oxime compounds (formaldehyde oxime, acetaldehyde oxime, acetone oxime, methyl ethyl ketone oxime, cyclohexanone oxime, etc., compounds having a structure represented by -C(=N-OH)- in the molecule), etc.
[0272] Among them, as the blocking agent having a dissociation temperature of 100° C. to 160° C., for example, at least one selected from oxime compounds is preferred from the viewpoint of storage stability.
[0273] For example, from the viewpoint of improving the brittleness of the film and improving the adhesion to the transfer target, the blocked isocyanate compound preferably has an isocyanurate structure.
[0274] The blocked isocyanate compound having an isocyanurate structure is obtained by, for example, isocyanurating hexamethylene diisocyanate and protecting it.
[0275] Among blocked isocyanate compounds having an isocyanurate structure, compounds having an oxime structure using an oxime compound as a blocking agent are also preferred from the viewpoints of being easier to set the dissociation temperature in a preferred range than compounds not having an oxime structure and being easier to reduce development residues.
[0276] For example, from the viewpoint of the strength of the cured film, the blocked isocyanate compound preferably has a polymerizable group, and more preferably has a radical polymerizable group.
[0277] The polymerizable group is not particularly limited, and a known polymerizable group can be used.
[0278] Examples of the polymerizable group include ethylenically unsaturated groups such as a (meth)acryloyloxy group, a (meth)acrylamide group, and a styryl group, and groups having an epoxy group such as a glycidyl group.
[0279] Among them, as the polymerizable group, from the viewpoint of the surface shape, development speed and reactivity in the obtained cured film, an ethylenically unsaturated group is preferred, a (meth)acryloyloxy group is more preferred, and an acryloyloxy group is particularly preferred.
[0280] As the blocked isocyanate compound, a commercially available product can be used.
[0281] Examples of commercially available blocked isocyanate compounds include Karenz (registered trademark) AOI-BM, Karenz (registered trademark) MOI-BM, Karenz (registered trademark) MOI-BP, etc. (all manufactured by SHOWA DENKO KK), and blocked Duranate series (for example, Duranate (registered trademark) TPA-B80E, manufactured by Asahi Kasei Corporation).
[0282] The photosensitive resin layer or the photosensitive resin composition may contain only one type of thermally crosslinkable compound, or may contain two or more types.
[0283] When a thermally crosslinkable compound is contained, the content of the thermally crosslinkable compound is preferably 1% by mass to 50% by mass, more preferably 5% by mass to 30% by mass, based on the total solid content of the photosensitive resin layer or the photosensitive resin composition.
[0284] The photosensitive resin layer of the transfer film of the present invention or the photosensitive resin composition forming the photosensitive resin layer preferably contains a compound capable of undergoing a Michael addition reaction, and more specifically, more preferably contains a thiol compound shown below, because the stamping processability of the cured film formed by curing the transferred photosensitive resin layer becomes better.
[0285] <Thiol Compounds>
[0286] As the thiol compound, a monofunctional thiol compound or a polyfunctional thiol compound is preferably used. Among them, from the viewpoint of hardness after curing, a thiol compound having two or more functions (polyfunctional thiol compound) is preferably contained, and a polyfunctional thiol compound is more preferred.
[0287] Here, the polyfunctional thiol compound refers to a compound having two or more mercapto groups (thiol groups) in the molecule.
[0288] The polyfunctional thiol compound is preferably a low molecular weight compound having a molecular weight of 100 or more, more preferably a molecular weight of 100 to 1,500, and even more preferably 150 to 1,000.
[0289] The number of functional groups of the polyfunctional thiol compound is preferably difunctional to decafunctional, more preferably difunctional to octafunctional, and even more preferably difunctional to hexafunctional, from the viewpoint of hardness after curing.
[0290] Furthermore, as the polyfunctional thiol compound, an aliphatic polyfunctional thiol compound is preferred from the viewpoints of tackiness and flex resistance and hardness after curing.
[0291] Furthermore, as the thiol compound, a secondary thiol compound is more preferred from the viewpoint of storage stability of the photosensitive transfer material.
[0292] Specific examples of the polyfunctional thiol compound include trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolethane tris(3-mercaptobutyrate), tris[(3-mercaptopropionyloxy)ethyl]isocyanurate, trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, esters), pentaerythritol tetrakis (3-mercaptopropionate), tetraethylene glycol bis (3-mercaptopropionate), dipentaerythritol hexa (3-mercaptopropionate), ethylene glycol dithiopropionate, 1,2-benzenedithiol, 1,3-benzenedithiol, 1,2-ethanedithiol, 1,3-propanedithiol, 1,6-hexamethylenedithiol, 2,2'-(ethylenedithio)diethanethiol, meso-2,3-dimercaptosuccinic acid, p-toluenedithiol, m-toluenedithiol, di(mercaptoethyl) ester, and the like.
[0293] Among these, preferred examples include trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolethane tris(3-mercaptobutyrate), tris[(3-mercaptopropionyloxy)ethyl]isocyanurate, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate) and dipentaerythritol hexa(3-mercaptopropionate).
[0294] As the monofunctional thiol compound, both aliphatic thiol compounds and aromatic thiol compounds can be used.
[0295] Specific examples of the monofunctional aliphatic thiol compound include 1-octanethiol, 1-dodecylthiol, β-mercaptopropionic acid, methyl-3-mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate.
[0296] Examples of the monofunctional aromatic thiol compound include thiophenol, toluenethiol, and xylenethiol.
[0297] From the viewpoint of tackiness and flex resistance and hardness after curing, the thiol compound is preferably a thiol compound having an ester bond, and more preferably a compound represented by the following formula 1.
[0298] [Chemical formula 7]
[0299]
[0300] In Formula 1, n represents an integer of 1 to 6, A represents an n-valent organic group having 1 to 15 carbon atoms or a group represented by the following Formula 2, and R 1 Each independently represents a divalent organic group having 1 to 15 carbon atoms.
[0301] [Chemical formula 8]
[0302]
[0303] In formula 2, R 2 ~R 4 Each independently represents a divalent organic group having 1 to 15 carbon atoms, and the wavy line portion represents a bonding position to an oxygen atom adjacent to A in the above formula 1. When A represents a group represented by the following formula 2, n represents 3.
[0304] From the viewpoint of hardness after curing, n in Formula 1 is preferably an integer of 2 to 6.
[0305] From the viewpoint of viscosity and bending resistance and hardness after curing, A in Formula 1 is preferably an n-valent aliphatic group having 1 to 15 carbon atoms or a group represented by the above-mentioned Formula 2, more preferably an n-valent aliphatic group having 4 to 15 carbon atoms or a group represented by the above-mentioned Formula 2, further preferably an n-valent aliphatic group having 4 to 10 carbon atoms or a group represented by the above-mentioned Formula 2, and particularly preferably a group represented by the above-mentioned Formula 2.
[0306] Furthermore, from the viewpoint of viscosity and bending resistance, hardness and moisture permeability after curing, A in Formula 1 is preferably an n-valent group including hydrogen atoms and carbon atoms or an n-valent group including hydrogen atoms, carbon atoms and oxygen atoms, more preferably an n-valent group including hydrogen atoms and carbon atoms, and particularly preferably an n-valent aliphatic hydrocarbon group.
[0307] From the viewpoint of viscosity and bending resistance and hardness after curing, R in Formula 1 1 Each of them independently is preferably an alkylene group having 1 to 15 carbon atoms, more preferably an alkylene group having 2 to 4 carbon atoms, further preferably an alkylene group having 3 carbon atoms, and particularly preferably a 1,2-propylene group. The alkylene group may be linear or branched.
[0308] From the viewpoint of viscosity and bending resistance and hardness after curing, R in Formula 2 2 ~R 4Each independently is preferably an aliphatic group having 2 to 15 carbon atoms, more preferably an alkylene group having 2 to 15 carbon atoms or a polyalkyleneoxyalkylene group having 3 to 15 carbon atoms, further preferably an alkylene group having 2 to 15 carbon atoms, and particularly preferably a vinyl group.
[0309] Furthermore, the polyfunctional thiol compound is preferably a compound having two or more groups represented by the following formula S-1.
[0310] [Chemical formula 9]
[0311]
[0312] In formula S-1, R 1S represents a hydrogen atom or an alkyl group, A 1S It represents -CO- or -CH2-, and the wavy part represents the bonding position with other structures.
[0313] As the polyfunctional thiol compound, a compound having 2 or more and 6 or less groups represented by the formula S-1 is preferred.
[0314] As R in formula S-1 1S The alkyl group in the above may be a linear, branched or cyclic alkyl group, and the number of carbon atoms is preferably 1 to 16, and more preferably 1 to 10. Specific examples of the alkyl group include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, 2-ethylhexyl, etc., and preferably methyl, ethyl, propyl or isopropyl.
[0315] As R 1S , particularly preferably a hydrogen atom, a methyl group, an ethyl group, a propyl group or an isopropyl group, and most preferably a methyl group or an ethyl group.
[0316] Furthermore, as the polyfunctional thiol compound, a compound represented by the following formula S-2 having a plurality of groups represented by the above formula S-1 is particularly preferred.
[0317] [Chemical formula 10]
[0318]
[0319] In formula S-2, R 1S Each independently represents a hydrogen atom or an alkyl group, A 1S Each independently represents -CO- or -CH2-, L 1S represents a linking group with a valence of nS, wherein nS represents an integer of 2 to 8. From the viewpoint of synthesis, R 1S are the same group, and preferably A 1S They are all the same group.
[0320] R in formula S-21S With R in the above formula S-1 1S The meanings and preferred ranges of nS are the same as those of nS.
[0321] L as the nS-valent linking group in Formula S-2 1S For example, there can be mentioned divalent linking groups such as -(CH2)mS- (mS represents an integer from 2 to 6), -(CH2)mS{(CH2)mSO}mT(CH2)mS- (mS and mT each independently represent an integer from 2 to 6), trivalent linking groups such as a trimethylolpropane residue, an isocyanuric acid ring having three -(CH2)pS- (pS represents an integer from 2 to 6), tetravalent linking groups such as a pentaerythritol residue, and pentavalent or hexavalent linking groups such as a dipentaerythritol residue.
[0322] Specifically, the following compounds are preferably mentioned as the thiol compound, but it is needless to say that the thiol compound is not limited to these compounds.
[0323] [Chemical formula 11]
[0324]
[0325] [Chemical formula 12]
[0326]
[0327] <Heterocyclic Compounds>
[0328] The photosensitive resin layer of the transfer film of the present invention or the photosensitive resin composition forming the photosensitive resin layer preferably contains a heterocyclic compound.
[0329] The heterocyclic compound contributes to improving the adhesion to a substrate (especially a copper substrate) and the corrosion resistance of a metal (especially copper).
[0330] The heterocyclic ring of the heterocyclic compound may be either a monocyclic ring or a polycyclic ring.
[0331] Examples of the hetero atom possessed by the heterocyclic compound include a nitrogen atom, an oxygen atom, a sulfur atom, etc. The heterocyclic compound preferably has at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, and a sulfur atom, and more preferably has a nitrogen atom.
[0332] As the heterocyclic compound, for example, triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, triazine compounds, rhodanine compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds, benzoxazole compounds or pyrimidine compounds can be preferably mentioned. Among the above, the heterocyclic compound is preferably at least one compound selected from the group consisting of triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, triazine compounds, rhodanine compounds, thiazole compounds, benzimidazole compounds and benzoxazole compounds, and more preferably at least one compound selected from the group consisting of triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds and benzoxazole compounds.
[0333] Preferred specific examples of the heterocyclic compound are shown below. As the triazole compound and the benzotriazole compound, the following compounds can be exemplified.
[0334] [Chemical formula 13]
[0335]
[0336] As the tetrazole compound, the following compounds can be exemplified.
[0337] [Chemical formula 14]
[0338]
[0339] As the thiadiazole compound, the following compounds can be exemplified.
[0340] [Chemical formula 15]
[0341]
[0342] As the triazine compound, the following compounds can be exemplified.
[0343] [Chemical formula 16]
[0344]
[0345] Examples of the rhodanine compound include the following compounds.
[0346] [Chemical formula 17]
[0347]
[0348] As the thiazole compound, the following compounds can be exemplified.
[0349] [Chemical formula 18]
[0350]
[0351] As the benzothiazole compound, the following compounds can be exemplified.
[0352] [Chemical formula 19]
[0353]
[0354] Examples of the benzimidazole compound include the following compounds.
[0355] [Chemical formula 20]
[0356]
[0357] As the benzoxazole compound, the following compounds can be exemplified.
[0358] [Chemical formula 21]
[0359]
[0360] The photosensitive resin layer or the photosensitive resin composition may contain only one type of heterocyclic compound, or may contain two or more types.
[0361] When containing a heterocyclic compound, the content of the heterocyclic compound is preferably 0.01% to 20% by mass, more preferably 0.1% to 10% by mass, further preferably 0.3% to 8% by mass, and particularly preferably 0.5% to 5% by mass, relative to the total solid content of the photosensitive resin layer or the photosensitive resin composition. When the content of the heterocyclic compound is within the above range, the adhesion to the substrate (especially the copper substrate) and the corrosion resistance of the metal (especially copper) can be improved.
[0362] <Surfactant>
[0363] The photosensitive resin layer of the transfer film of the present invention or the photosensitive resin composition forming the photosensitive resin layer may contain a surfactant.
[0364] The surfactant is not particularly limited, and a known surfactant can be used.
[0365] Examples of the surfactant include surfactants described in paragraph 0017 of Japanese Patent No. 4502784 and paragraphs 0060 to 0071 of Japanese Patent Application Laid-Open No. 2009-237362.
[0366] As the surfactant, a fluorine-based surfactant or a silicon-based surfactant is preferred.
[0367] As an example of a commercially available product of the fluorine-based surfactant, MEGAFACE (registered trademark) F551A (manufactured by DIC Corporation) can be mentioned.
[0368] Examples of commercially available fluorine-based surfactants include MEGAFACE F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-475, F-477, F-479, F-482, F-551-A, F-552, F-554, F-555-A, F-556, F-557, F-558, F-559, F-600, F-601, F-602, F-603, F-604, F-605, F-606, F-607, F-608, F-609, F-610, F-611, F-612, F-613, F-614, F-615, F-616, F-617, F-618, F-619, F-620, F-621 59. F-560, F-561, F-565, F-563, F-568, F-575, F-780, EXP, MFS-330, R-41, R-41 -LM, R-01, R-40, R-40-LM, RS-43, TF-1956, RS-90, R-94, RS-72-K, DS-21 (above, DIC Corporation), FLUORAD FC430, FC431, FC171 (all manufactured by Sumitomo 3M Limited), SURFLON S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393, KH-40 (all manufactured by AGC Inc.), PolyFox PF636, PF656, PF6320, PF6520, PF7002 (all manufactured by OMNOVA Solutions Inc.), FTERGENT 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, 245F (all manufactured by NEOS COMPANY LIMITED), etc.
[0369] In addition, the fluorine-based surfactant has a molecular structure with a functional group containing a fluorine atom, and an acrylic compound can also be preferably used. When heat is applied to the acrylic compound, a part of the functional group containing a fluorine atom is cleaved and the fluorine atom is volatilized. As such a fluorine-based surfactant, MEGAFACE DS series manufactured by DIC Corporation (Chemical Industry Daily (February 22, 2016), Nikkei Industry News (February 23, 2016)), such as MEGAFACE DS-21, can be cited.
[0370] Furthermore, as the fluorine-based surfactant, it is also preferable to use a polymer of a fluorine atom-containing vinyl ether compound having a fluorinated alkyl group or a fluorinated alkylene ether group and a hydrophilic vinyl ether compound.
[0371] The fluorine-based surfactant can also be a block polymer. The fluorine-based surfactant can also preferably be a fluorine-containing polymer compound containing a repeating unit derived from a (meth)acrylate compound having a fluorine atom, and a repeating unit derived from a (meth)acrylate compound having two or more (preferably five or more) alkyleneoxy groups (preferably ethyleneoxy and propyleneoxy).
[0372] As the fluorine-based surfactant, a fluorine-containing polymer having an ethylenically unsaturated bond-containing group in a side chain may be used, and examples thereof include MEGAFACE RS-101, RS-102, RS-718K, and RS-72-K (all manufactured by DIC Corporation).
[0373] Examples of the nonionic surfactant include glycerin, trimethylolpropane, trimethylolethane, and ethoxylates and propoxylates thereof (e.g., glycerin propoxylate, glycerin ethoxylate, etc.), polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyethylene glycol dilaurate, polyethylene glycol distearate, sorbitan fatty acid esters, Pluronic L10, L31, L61, L62, 10R5, 17R2, 25R2 (above, manufactured by BASF), Tetronic 304, 701, 704, 901, 904, 150R1 (above, manufactured by BASF), Solsperse 20000 (above, manufactured by The Lubrizol Corporation), NCW-101, NCW-1001, NCW-1002 (above, manufactured by FUJIFILM Wako Pure Chemical Corporation), Pionin D-6112, D-6112-W, D-6315 (all manufactured by Takemoto Oil & Fat Co., Ltd.), Olfine E1010, Surfynol 104, 400, 440 (all manufactured by Nissin Chemical Co., Ltd.), etc.
[0374] Examples of the silicon-based surfactant include linear polymers including a siloxane bond and modified siloxane polymers having an organic group introduced into a side chain or a terminal.
[0375] Examples of commercially available silicone surfactants include DOWSIL 8032 ADDITIVE, Toray Silicone DC3PA, Toray Silicone SH7PA, Toray Silicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray Silicone SH29PA, Toray Silicone SH30PA, and Toray Silicone SH8400 (all commercially available products of Dow Corning Toray Co., Ltd.), X-22-4952, X-22-4272, X-22-6266, KF-351A, K354L, KF-355A, KF-945, KF-640, KF-642, KF-643, X-22-6191, X-22-4515, KF-6004, KP-341, KF-6001, KF-6002 (above, manufactured by Shin-Etsu Chemical Co., Ltd.), F-4440, TSF-4300, TSF-4445, TSF-4460, TSF-4452 (above, manufactured by Momentive Performance Materials Inc.), BYK307, BYK323, BYK330 (above, BYK Co., Ltd.) etc. DOWSIL (registered trademark) 8032 (manufactured by Dow Toray Co., Ltd.) can be mentioned.
[0376] Silicon-based surfactants are preferred because a protective film described later can be easily pressed and peeled off from the photosensitive resin layer.
[0377] The photosensitive resin layer or the photosensitive resin composition may contain only one type of surfactant, or may contain two or more types.
[0378] When a surfactant is contained, the content of the surfactant is preferably 0.01 to 3 mass %, more preferably 0.05 to 1 mass %, and further preferably 0.1 to 0.8 mass % relative to the total solid content of the photosensitive resin layer or the photosensitive resin composition.
[0379] <Hydrogen Donating Compound>
[0380] The photosensitive resin layer of the transfer film of the present invention or the photosensitive resin composition forming the photosensitive resin layer preferably contains a hydrogen donating compound.
[0381] Here, the hydrogen-donating compound has the functions of further increasing the sensitivity of the photopolymerization initiator to the activating light and suppressing the polymerization disorder of the polymerizable compound due to oxygen.
[0382] Examples of the hydrogen-donating compound include amines, for example, compounds described in "Journal of Polymer Society" by MR Sander et al., Vol. 10, p. 3173 (1972), Japanese Patent Publication No. 44-20189, Japanese Patent Application Publication No. 51-82102, Japanese Patent Application Publication No. 52-134692, Japanese Patent Application Publication No. 59-138205, Japanese Patent Application Publication No. 60-84305, Japanese Patent Application Publication No. 62-18537, Japanese Patent Application Publication No. 64-33104, Research Disclosure No. 33825, etc.
[0383] Specific examples of the hydrogen-donating compound include triethanolamine, ethyl p-dimethylaminobenzoate, p-formyldimethylaniline, and p-methylthiodimethylaniline.
[0384] In addition, examples of hydrogen-donating compounds include amino acid compounds (N-phenylglycine, etc.), organic metal compounds described in Japanese Patent Publication No. 48-42965 (tributyltin acetate, etc.), hydrogen donors described in Japanese Patent Publication No. 55-34414, and sulfur compounds described in Japanese Patent Application Laid-Open No. 6-308727 (trithiane, etc.).
[0385] The photosensitive resin layer or the photosensitive resin composition may contain only one type of hydrogen-donating compound, or may contain two or more types.
[0386] In the case of containing a hydrogen donating compound, for example, from the viewpoint of improving the curing rate by balancing the polymerization growth rate and the chain transfer, the content of the hydrogen donating compound is preferably 0.01% by mass to 10% by mass, more preferably 0.03% by mass to 5% by mass, and further preferably 0.05% by mass to 3% by mass relative to the total solid content of the photosensitive resin layer or the photosensitive resin composition.
[0387] <Solvent>
[0388] The photosensitive resin composition forming the photosensitive resin layer of the transfer film of the present invention preferably contains a solvent.
[0389] When the photosensitive resin composition contains a solvent, it tends to be easy to form a photosensitive resin layer by coating.
[0390] As the solvent, any commonly used solvent can be used without particular limitation.
[0391] As the solvent, an organic solvent is preferred.
[0392] Examples of the organic solvent include methyl ethyl ketone, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate (also known as 1-methoxy-2-propyl acetate), diethylene glycol ethyl methyl ether, cyclohexanone, methyl isobutyl ketone, ethyl lactate, methyl lactate, caprolactam, n-propanol, and 2-propanol.
[0393] The solvent is preferably a mixed solvent of methyl ethyl ketone and propylene glycol monomethyl ether acetate or a mixed solvent of diethylene glycol ethyl methyl ether and propylene glycol monomethyl ether acetate.
[0394] As the solvent, Solvent described in paragraphs 0054 and 0055 of US Patent Application Publication No. 2005 / 282073 can also be used, and the contents of this specification are incorporated into the present invention.
[0395] Furthermore, as the solvent, an organic solvent (high boiling point solvent) having a boiling point of 180° C. to 250° C. may be used as necessary.
[0396] When the photosensitive resin composition contains a solvent, it may contain only one kind of solvent or two or more kinds of solvents.
[0397] When containing a solvent, the solid content of the photosensitive resin composition is preferably 5 to 80% by mass, more preferably 5 to 40% by mass, and particularly preferably 5 to 30% by mass, based on the total mass of the photosensitive resin composition.
[0398] When the photosensitive resin composition contains a solvent, for example, from the viewpoint of coating properties, the viscosity of the photosensitive resin composition at 25° C. is preferably 1 to 50 mPa·s, more preferably 2 to 40 mPa·s, and further preferably 3 to 30 mPa·s.
[0399] The viscosity is measured using a viscometer. As a viscometer, for example, a viscometer manufactured by TOKISANGYO CO., LTD. (trade name: VISCOMETER TV-22) can be preferably used. However, the viscometer is not limited thereto.
[0400] When the photosensitive resin composition contains a solvent, for example, from the viewpoint of coating properties, the surface tension of the photosensitive resin composition at 25° C. is preferably 5 to 100 mN / m, more preferably 10 to 80 mN / m, and further preferably 15 to 40 mN / m.
[0401] The surface tension is measured using a surface tensiometer. As the surface tensiometer, for example, a surface tensiometer (trade name: Automatic Surface Tensiometer CBVP-Z) manufactured by Kyowa Interface Science Co., Ltd. can be preferably used. However, the surface tensiometer is not limited to this.
[0402] <Other ingredients>
[0403] The photosensitive resin layer of the transfer film of the present invention or the photosensitive resin composition forming the photosensitive resin layer may contain components other than the components described above (so-called other components).
[0404] Examples of other components include particles (for example, metal oxide particles) and colorants.
[0405] In addition, examples of other components include the thermal polymerization inhibitor described in paragraph 0018 of Japanese Patent No. 4502784 and other additives described in paragraphs 0058 to 0071 of Japanese Patent Application Laid-Open No. 2000-310706.
[0406] -particle-
[0407] The photosensitive resin layer or the photosensitive resin composition may contain particles (for example, metal oxide particles; the same shall apply hereinafter) for the purpose of adjusting the refractive index, light transmittance, etc.
[0408] The metals in the metal oxide particles also include semi-metals such as B, Si, Ge, As, Sb, and Te.
[0409] For example, from the viewpoint of transparency of the cured film, the average primary particle size of the particles is preferably 1 nm to 200 nm, and more preferably 3 nm to 80 nm.
[0410] The average primary particle size of the particles is calculated by measuring the particle sizes of 200 random particles using an electron microscope and taking the arithmetic average of the measurement results. In addition, when the shape of the particles is not spherical, the longest side is used as the particle size.
[0411] When the photosensitive resin layer or the photosensitive resin composition contains particles, the particles may contain only one type of particles having different metal species, sizes, etc., or may contain two or more types of particles having different metal species, sizes, etc.
[0412] The photosensitive resin layer or the photosensitive resin composition preferably contains no particles, or the content of particles relative to the total solid content of the photosensitive resin layer or the photosensitive resin composition is greater than 0 mass % and less than 35 mass %, more preferably contains no particles, or the content of particles relative to the total solid content of the photosensitive resin layer or the photosensitive resin composition is greater than 0 mass % and less than 10 mass %, further preferably contains no particles, or the content of particles relative to the total solid content of the photosensitive resin layer or the photosensitive resin composition is greater than 0 mass % and less than 5 mass %, further preferably contains no particles, or the content of particles relative to the total solid content of the photosensitive resin layer or the photosensitive resin composition is greater than 0 mass % and less than 1 mass %, and particularly preferably contains no particles.
[0413] -Colorants-
[0414] The photosensitive resin layer or the photosensitive resin composition may contain a trace amount of a colorant (a pigment, a dye, etc.), but preferably contains substantially no colorant, for example, from the viewpoint of transparency.
[0415] When a colorant is contained, the content of the colorant is preferably less than 1% by mass, more preferably less than 0.1% by mass, based on the total solid content of the photosensitive resin layer or the photosensitive resin composition.
[0416] The thickness of the photosensitive resin layer is not particularly limited, but is preferably 20 μm or less, more preferably 15 μm or less, and further preferably 12 μm or less.
[0417] When the thickness of the photosensitive resin layer is 20 μm or less, it is advantageous in terms of forming the entire transfer film, improving the transmittance of the photosensitive resin layer or the obtained cured film, and suppressing yellowing of the photosensitive resin layer or the obtained cured film.
[0418] The thickness of the photosensitive resin layer is preferably 1 μm or more, more preferably 2 μm or more, and particularly preferably 3 μm or more, from the viewpoint of production suitability, for example.
[0419] The thickness of the photosensitive resin layer was calculated as an average value of five arbitrary points measured by cross-sectional observation using a scanning electron microscope (SEM).
[0420] The refractive index of the photosensitive resin layer is not particularly limited, but is preferably 1.47 to 1.56, more preferably 1.50 to 1.53, further preferably 1.50 to 1.52, and particularly preferably 1.51 to 1.52.
[0421] The photosensitive resin layer is preferably achromatic. Specifically, total reflection (incident angle 8°, light source: D-65 (2° field of view)) is CIE1976 (L * , a * , b* ) color space, L * The value is preferably 10 to 90, a * The value is preferably -1.0 to 1.0, b * The value is preferably -1.0 to 1.0.
[0422] The method for forming the photosensitive resin layer is not particularly limited, and a known method can be used.
[0423] As an example of a method for forming a photosensitive resin layer, there is mentioned a method of forming a photosensitive resin layer by applying a photosensitive resin composition containing a solvent onto a temporary support and drying the composition as necessary.
[0424] As the coating method, a known method can be used.
[0425] Examples of the coating method include a printing method, a spray coating method, a roll coating method, a rod coating method, a curtain coating method, a spin coating method, and a die coating method (ie, a slit coating method).
[0426] Among them, as a coating method, a die coating method is preferred.
[0427] As the drying method, known methods such as natural drying, heat drying, and reduced pressure drying can be used, and these methods can be used alone or in combination of a plurality of them.
[0428] In the present invention, "drying" means removing at least a part of the solvent contained in the composition.
[0429] 〔Protective film〕
[0430] The transfer film of the present invention has a protective film.
[0431] Examples of the protective film include polyethylene terephthalate films, polypropylene films, polystyrene films, and polycarbonate films.
[0432] As the protective film, for example, the films described in paragraphs 0083 to 0087 and paragraph 0093 of JP-A-2006-259138 can be used.
[0433] The protective film of the transfer film of the present invention has an arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of 150 nm or less, preferably 1 to 80 nm, and more preferably 1 to 30 nm.
[0434] In the present invention, from the viewpoint of adjusting the arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of the protective film to the above range, particles may be contained in the protective film, and the layer structure contained in the temporary support may have a particle-containing layer constituting the surface on the photosensitive resin layer side.
[0435] Examples of the particles contained in the protective film (particularly, the particle-containing layer) include the same particles as exemplified as the particles contained in the temporary support.
[0436] In the present invention, it is preferred to satisfy the following formula (2) because the releasability of the temporary support and the protective film and the punching workability of the cured film formed by curing the transferred photosensitive resin layer can be achieved at a higher level.
[0437] Y≤Z Formula (2)
[0438] Here, in formula (2), Y represents the value (nm) of the arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of the temporary support, and Z represents the value (nm) of the arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of the protective film.
[0439] 〔Refractive Index Adjustment Layer〕
[0440] The transfer film of the present invention may further include a refractive index adjusting layer having a higher refractive index than the photosensitive resin layer between the photosensitive resin layer and the protective film.
[0441] The refractive index of the refractive index adjusting layer is preferably 1.50 or more, more preferably 1.55 or more, further preferably 1.60 or more, and particularly preferably 1.70 or more.
[0442] The upper limit of the refractive index of the refractive index adjusting layer is not particularly limited, but is preferably 2.10 or less, more preferably 1.85 or less, further preferably 1.78 or less, and particularly preferably 1.74 or less.
[0443] The refractive index adjusting layer may be photocurable (ie, photosensitivity), thermosetting, or both. However, from the viewpoint of forming a cured film having excellent strength, the refractive index adjusting layer is preferably photocurable.
[0444] The refractive index adjusting layer preferably has alkali solubility (for example, solubility in a weak alkali aqueous solution).
[0445] The thickness of the refractive index adjusting layer is not particularly limited.
[0446] The thickness of the refractive index adjustment layer is preferably 50 nm to 500 nm, more preferably 55 nm to 110 nm, and even more preferably 60 nm to 100 nm.
[0447] The thickness of the refractive index adjusting layer was calculated as an average value of five arbitrary points measured by cross-sectional observation using a scanning electron microscope (SEM).
[0448] The method for controlling the refractive index of the refractive index adjusting layer is not particularly limited, and examples thereof include a method of using a resin having a predetermined refractive index alone, a method of using a resin and metal oxide particles or metal particles, and a method of using a composite of a metal salt and a resin.
[0449] The type of the metal oxide particles is not particularly limited, and known metal oxide particles can be used.
[0450] Specifically, the metal oxide particles are preferably at least one selected from the group consisting of zirconium oxide particles (ZrO 2 particles), Nb 2 O 5 particles, titanium oxide particles (TiO 2 particles) and silicon dioxide particles (SiO 2 particles).
[0451] Among them, as the metal oxide particles, for example, from the viewpoint of easily adjusting the refractive index of the refractive index adjusting layer to 1.6 or more, at least one selected from the group consisting of zirconium oxide particles and titanium oxide particles is more preferred. For example, from the viewpoint of transparency of the cured film, the average primary particle size of the particles is preferably 1 nm to 200 nm, and more preferably 3 nm to 80 nm.
[0452] The average primary particle size of the particles is calculated by measuring the particle sizes of 200 random particles using an electron microscope and taking the arithmetic average of the measurement results. In addition, when the shape of the particles is not spherical, the longest side is used as the particle size.
[0453] When the refractive index adjusting layer contains metal oxide particles, the refractive index adjusting layer may contain only one type of metal oxide particles, or may contain two or more types of metal oxide particles.
[0454] Examples of commercially available metal oxide particles include
[0455] Calcined zirconium oxide particles (manufactured by CIK-Nano Tek., trade name: ZRPGM15WT%-F04), calcined zirconium oxide particles (manufactured by CIK-Nano Tek., trade name: ZRPGM15WT%-F74), calcined zirconium oxide particles (manufactured by CIK-Nano Tek., trade name: ZRPGM15WT%-F75), calcined zirconium oxide particles (manufactured by CIK-Nano Tek., trade name: ZRPGM15WT%-F76),
[0456] Zirconia particles (NanoUse OZ-S30M, manufactured by Nissan Chemical Corporation)
[0457] Zirconium oxide particles (NanoUse OZ-S30K, manufactured by Nissan Chemical Corporation).
[0458] From the viewpoint of improving the concealment of concealed objects such as electrode patterns and effectively improving the visibility of the concealed objects, the content of metal oxide particles is preferably 1% to 95% by mass, more preferably 20% to 90%, and even more preferably 40% to 85% by mass, relative to the total mass of the refractive index adjustment layer.
[0459] When titanium oxide is used as the metal oxide particles, the content of the titanium oxide particles is preferably 1 to 95% by mass, more preferably 20 to 90%, and even more preferably 40 to 85% by mass, based on the total mass of the refractive index adjusting layer.
[0460] Furthermore, the refractive index adjusting layer preferably contains a binder polymer and an ethylenically unsaturated compound.
[0461] Regarding the components of the refractive index adjusting layer, reference can be made to the components of the curable second resin layer described in paragraphs 0019 to 0040 and paragraphs 0144 to 0150 of JP-A-2014-108541, the components of the transparent layer described in paragraphs 0024 to 0035 and paragraphs 0110 to 0112 of JP-A-2014-10814, and the components of the composition having an ammonium salt described in paragraphs 0034 to 0056 of International Publication No. 2016 / 009980.
[0462] As the binder polymer contained in the refractive index adjusting layer, the same binder polymer as the binder polymer contained in the photosensitive resin layer can be used, and the preferred range is also the same.
[0463] As the ethylenically unsaturated compound contained in the refractive index adjusting layer, the same ethylenically unsaturated compound as the radical polymerizable compound having an ethylenically unsaturated compound contained in the photosensitive resin layer can be used, and the preferred range is also the same.
[0464] Furthermore, from the viewpoint of suppressing oxidation of metal in contact with the refractive index adjusting layer, the refractive index adjusting layer preferably contains at least one metal antioxidant.
[0465] As the metal antioxidant, preferably, for example, a compound having an aromatic ring containing a nitrogen atom in the molecule is used.
[0466] Examples of the metal antioxidant include imidazole, benzimidazole, tetrazole, mercaptothiadiazole, and benzotriazole.
[0467] The refractive index adjusting layer may contain other components besides the above-mentioned components.
[0468] As other components that may be contained in the refractive index adjusting layer, the same components as those contained in the photosensitive resin layer described above may be mentioned.
[0469] The refractive index adjusting layer preferably contains a surfactant as another component.
[0470] The refractive index adjustment layer is preferably achromatic. Specifically, total reflection (incident angle 8°, light source: D-65 (2° field of view)) is CIE1976 (L * , a * , b * ) color space, L * The value is preferably 10 to 90, a * The value is preferably -1.0 to 1.0, b * The value is preferably -1.0 to 1.0.
[0471] There is no particular limitation on the method for forming the refractive index adjusting layer.
[0472] An example of a method for forming the refractive index adjusting layer is a method of coating the refractive index adjusting layer-forming composition containing an aqueous solvent on the above-mentioned photosensitive resin layer formed on the temporary support and drying the composition as necessary.
[0473] Specific examples of the coating and drying methods in the method for forming the refractive index adjusting layer are respectively the same as the specific examples of the coating and drying methods in the method for forming the photosensitive resin layer.
[0474] 〔Thermoplastic resin layer〕
[0475] The transfer film of the present invention may further include a thermoplastic resin layer between the temporary support and the photosensitive resin layer.
[0476] If the transfer film also has a thermoplastic resin layer, when the transfer film is transferred to a substrate to form a laminate, bubbles caused by lamination are not easily generated. When the laminate is used in an image display device, image unevenness is not easily generated, and excellent display characteristics can be obtained.
[0477] The thermoplastic resin layer preferably has alkali solubility.
[0478] The thermoplastic resin layer functions as a buffer material that absorbs the unevenness of the substrate surface during transfer.
[0479] The unevenness on the substrate surface also includes formed images, electrodes, wiring, etc.
[0480] The thermoplastic resin layer preferably has a property of being deformable in accordance with the irregularities.
[0481] The thermoplastic resin layer preferably contains an organic polymer described in Japanese Unexamined Patent Publication No. 5-72724, and more preferably contains an organic polymer having a softening point of about 80° C. or less according to the Vicat method (specifically, the polymer softening point measurement method according to ASTM D 1235).
[0482] The thickness of the thermoplastic resin layer is, for example, preferably 3 μm to 30 μm, more preferably 4 μm to 25 μm, and further preferably 5 μm to 20 μm.
[0483] When the thickness of the thermoplastic resin layer is 3 μm or more, the ability to follow the irregularities on the substrate surface is further improved, and thus the irregularities on the substrate surface can be absorbed more effectively.
[0484] When the thickness of the thermoplastic resin layer is 30 μm or less, the manufacturing adaptability is further improved, so that, for example, the load of drying (so-called drying for removing the solvent) when the thermoplastic resin layer is coated on the temporary support is further reduced, and the development time of the thermoplastic resin layer after transfer is further shortened.
[0485] The thickness of the thermoplastic resin layer was calculated as an average value of five arbitrary points measured by cross-sectional observation using a scanning electron microscope (SEM).
[0486] The thermoplastic resin layer can be formed by applying a thermoplastic resin layer-forming composition containing a solvent and a thermoplastic organic polymer onto a temporary support and drying the composition as necessary.
[0487] Specific examples of the coating and drying methods in the method for forming the thermoplastic resin layer are respectively the same as the specific examples of the coating and drying methods in the method for forming the photosensitive resin layer.
[0488] The solvent is not particularly limited as long as it dissolves the polymer component forming the thermoplastic resin layer.
[0489] Examples of the solvent include organic solvents (for example, methyl ethyl ketone, cyclohexanone, propylene glycol monomethyl ether acetate, n-propanol, and 2-propanol).
[0490] The viscosity of the thermoplastic resin layer measured at 100° C. is preferably 1,000 Pa·s to 10,000 Pa·s. Also, the viscosity of the thermoplastic resin layer measured at 100° C. is preferably lower than the viscosity of the photosensitive resin layer measured at 100° C.
[0491] [Middle level]
[0492] The transfer film of the present invention may further include an intermediate layer between the temporary support and the photosensitive resin layer.
[0493] When the transfer film of the present invention has a thermoplastic resin layer, the intermediate layer is preferably disposed between the thermoplastic resin layer and the photosensitive resin layer.
[0494] Examples of the component contained in the intermediate layer include at least one polymer selected from the group consisting of polyvinyl alcohol, polyvinyl pyrrolidone, and cellulose.
[0495] Furthermore, as the middle layer, an intermediate layer described as a “separation layer” in Japanese Patent Application Laid-Open No. 5-72724 can also be used.
[0496] In the case of manufacturing a transfer film having a thermoplastic resin layer, an intermediate layer and a photosensitive resin layer in sequence on a temporary support, the intermediate layer can be formed, for example, by applying a solvent that does not dissolve the thermoplastic resin layer and an intermediate layer forming composition containing the above-mentioned polymer as a component of the intermediate layer and drying it as needed.
[0497] In detail, first, a thermoplastic resin layer-forming composition is applied to a temporary support, and dried as needed to form a thermoplastic resin layer. Next, an intermediate layer-forming composition is applied to the formed thermoplastic resin layer, and dried as needed to form an intermediate layer. Next, a photosensitive resin composition (so-called photosensitive resin layer-forming composition) containing an organic solvent is applied to the formed intermediate layer, and dried to form a photosensitive resin layer. In addition, the organic solvent contained in the photosensitive resin layer-forming composition is preferably an organic solvent that does not dissolve the intermediate layer.
[0498] Specific examples of the coating and drying methods in the method for forming the intermediate layer are respectively the same as the specific examples of the coating and drying methods in the method for forming the photosensitive resin layer.
[0499] -Impurities-
[0500] In the transfer film according to the present invention, from the viewpoint of improving reliability and pattern formability, it is preferred that the content of impurities in the photosensitive resin layer and the refractive index adjusting layer is small.
[0501] Specific examples of impurities include sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin and ions thereof, and halide ions (chloride ions, bromide ions, iodide ions, etc.). Among them, sodium ions, potassium ions, and chloride ions are not easily mixed as impurities, so it is particularly preferred to set the content to the following.
[0502] The content of impurities in each layer is preferably 1,000 ppm or less, more preferably 200 ppm or less, and particularly preferably 40 ppm or less, based on mass. The lower limit is not particularly limited, but from the perspective of the limit that can be reduced in reality or the measurement limit, based on mass, it can be set to 10 ppb or more, and can be set to 100 ppb or more.
[0503] As methods for reducing impurities to the above range, there can be cited methods of selecting materials for each layer that do not contain impurities, methods of preventing impurities from being mixed when forming layers, methods of removing impurities by washing, etc. By this method, the amount of impurities can be set within the above range.
[0504] Impurities can be quantified by a known method such as ICP (Inductively Coupled Plasma) emission spectrometry, atomic absorption spectrometry, or ion chromatography.
[0505] Furthermore, it is preferred that the content of compounds such as benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, hexane, etc. in each layer is small. The content of these compounds in each layer is preferably 1,000 ppm or less, more preferably 200 ppm or less, and particularly preferably 40 ppm or less, based on a mass basis. The lower limit is not particularly limited, but from the perspective of the limit that can be reduced in reality or the measurement limit, it can be set to 10 ppb or more, and can be set to 100 ppb or more, based on a mass basis.
[0506] The content of impurities in the compound can be controlled by the same method as the above-mentioned metal impurities, and can be quantified by a known measurement method.
[0507] - Specific example of transfer film -
[0508] Figure 1 This is a schematic cross-sectional view showing an example of the transfer film of the present invention.
[0509] like Figure 1 As shown, the transfer film 10 has a laminated structure of protective film 16 / refractive index adjusting layer 20A / photosensitive resin layer 18A / temporary support 12 (i.e., a laminated structure in which temporary support 12, photosensitive resin layer 18A, refractive index adjusting layer 20A, and protective film 16 are arranged in this order).
[0510] However, the transfer film of the present invention is not limited to the transfer film 10, and for example, the refractive index adjustment layer 20A may be omitted. In addition, at least one of the thermoplastic resin layer and the intermediate layer described above may be provided between the temporary support 12 and the photosensitive resin layer 18A.
[0511] The refractive index adjustment layer 20A is a layer disposed on the side opposite to the side where the temporary support 12 is present when viewed from the photosensitive resin layer 18A, and has a refractive index of 1.50 or more at a wavelength of 550 nm.
[0512] The transfer film 10 is a negative type material (so-called negative type film).
[0513] The method for producing the transfer film 10 is not particularly limited.
[0514] The method for producing the transfer film 10 includes, for example, the steps of forming the photosensitive resin layer 18A on the temporary support 12 , forming the refractive index adjusting layer 20A on the photosensitive resin layer 18A, and forming the protective film 16 on the refractive index adjusting layer 20A in this order.
[0515] The method for producing the transfer film 10 may include a step of volatilizing ammonia as described in paragraph 0056 of International Publication No. 2016 / 009980 between the step of forming the refractive index adjusting layer 20A and the step of forming the protective film 16 .
[0516] 〔use〕
[0517] The use of the transfer film of the present invention is not particularly limited. The temporary support and the protective film have excellent releasability, and the cured film formed by curing the transferred photosensitive resin layer has excellent stamping processability. Therefore, it can be preferably used as a transfer film for touch panels, and can be more preferably used as a transfer film for forming a protective film in a touch panel, and can be particularly preferably used as a transfer film for forming an electrode protective film in a touch panel.
[0518] [Method for producing laminated body]
[0519] The method for producing a laminate of the present invention comprises:
[0520] a first peeling step of peeling off the protective film from the transfer film of the present invention;
[0521] A transfer step of transferring the transfer film after the protective film is peeled off from the photosensitive resin layer side to a substrate having an electrode;
[0522] a curing step of curing at least a portion of the transferred photosensitive resin layer to form a cured film; and
[0523] After the curing step, the temporary support is peeled off to obtain a laminated body in which the cured film is laminated on the substrate having the electrode.
[0524] In addition, specific methods in the first peeling step, transfer step, and second peeling step of the manufacturing method of the laminate of the present invention can be the same as the first peeling step, transfer step, and second peeling step of the manufacturing method of the touch panel of the present invention described later.
[0525] The laminate produced by the method for producing a laminate of the present invention is a laminate in which a photosensitive resin layer included in the transfer film of the present invention is transferred onto a substrate having an electrode, and a cured film is laminated thereon.
[0526] The substrate having electrodes is preferably a substrate including electrodes of a capacitive input device.
[0527] Furthermore, the electrodes of the capacitive input device may be transparent electrode patterns or may be routing wirings.
[0528] As the electrostatic capacitance input device, a touch panel is preferably used.
[0529] As the touch panel electrode, for example, a transparent electrode pattern arranged at least in the image display region of the touch panel can be cited. The touch panel electrode can extend from the image display region to the frame of the touch panel.
[0530] As the wiring for the touch panel, for example, there is a routing wiring (so-called lead-out wiring) arranged in the frame portion of the touch panel.
[0531] As a form of the touch panel substrate and the touch panel, a form in which a part of the routing wiring is stacked on a portion of the transparent electrode pattern extending to the frame portion of the touch panel to electrically connect the transparent electrode pattern and the routing wiring is preferably used.
[0532] As a material of the transparent electrode pattern, a metal oxide film such as ITO (indium tin oxide) and IZO (indium zinc oxide), or a metal mesh, a metal fine wire such as a silver nanowire, etc. is preferable.
[0533] Examples of the metal thin wires include thin wires of silver, copper, and the like, of which silver conductive materials such as silver mesh and silver nanowires are preferred.
[0534] As a material of the routing wiring, metal is preferable.
[0535] As the metal of the material of the detour wiring, gold, silver, copper, molybdenum, aluminum, titanium, chromium, zinc and manganese and alloys containing two or more of these metal elements can be cited. As the material of the detour wiring, copper, molybdenum, aluminum or titanium is preferred, and copper is particularly preferred.
[0536] -First Specific Example of Touch Panel-
[0537] Figure 21 is a schematic cross-sectional view showing a first specific example of a touch panel having a photosensitive resin layer transferred using the transfer film of the present invention. More specifically, Figure 2 1 is a schematic cross-sectional view of an image display region of touch panel 30 .
[0538] like Figure 2 As shown, the touch panel 30 has a structure in which a substrate 32, a second refractive index adjustment layer 36, a transparent electrode pattern 34 as a touch panel electrode, a first refractive index adjustment layer 20, and a touch panel electrode protection film 18 are arranged in this order.
[0539] In the touch panel 30 , the touch panel electrode protection film 18 and the first refractive index adjustment layer 20 cover the entire transparent electrode pattern 34 .
[0540] The second refractive index adjusting layer 36 and the first refractive index adjusting layer 20 preferably cover the first region 40 where the transparent electrode pattern 34 exists and the second region 42 where the transparent electrode pattern 34 does not exist, directly or through other layers. In this way, the transparent electrode pattern 34 becomes more difficult to be visually recognized.
[0541] It is more preferable that the second refractive index adjusting layer 36 and the first refractive index adjusting layer 20 directly cover both the first region 40 and the second region 42 rather than covering both the first region 40 and the second region 42 via another layer.
[0542] Examples of “other layers” include insulating layers and electrode patterns other than the transparent electrode pattern 34 .
[0543] The first refractive index adjustment layer 20 is stacked over both the first region 40 and the second region 42. The first refractive index adjustment layer 20 is adjacent to the second refractive index adjustment layer 36, and further, is adjacent to the transparent electrode pattern 34.
[0544] The shape of the end portion of the transparent electrode pattern 34 in the portion in contact with the second refractive index adjusting layer 36 is as follows: Figure 2 In the case of the tapered shape shown, it is preferable to laminate the first refractive index adjustment layer 20 along the tapered shape (that is, with the same slope as the tapered angle).
[0545] As the transparent electrode pattern 34, an ITO transparent electrode pattern is preferable.
[0546] The transparent electrode pattern 34 can be formed by, for example, the following method.
[0547] On the substrate 32 on which the second refractive index adjustment layer 36 is formed, an electrode film (e.g., an ITO film) is formed by sputtering. Next, on the formed electrode film, an etching protective layer is formed by coating an etching photosensitive resist or by transferring the etching photosensitive film. Next, the formed etching protective layer is patterned into a desired pattern shape by exposure and development. Next, the portion of the electrode film that is not covered by the patterned etching protective layer is removed by etching, and the electrode film is patterned into a desired shape (i.e., a transparent electrode pattern 34). Next, the etching protective layer patterned by the stripping solution is removed.
[0548] - Second specific example of touch panel -
[0549] Figure 3 This is a schematic cross-sectional view showing a second specific example of a touch panel having a photosensitive resin layer transferred using the transfer film of the present invention.
[0550] like Figure 3 As shown, the touch panel 90 includes an image display area 74 and an image non-display area 75 (ie, a frame portion).
[0551] Furthermore, the touch panel 90 includes touch panel electrodes on both surfaces of the substrate 32. Specifically, the touch panel 90 includes a first transparent electrode pattern 70 on one surface of the substrate 32 and a second transparent electrode pattern 72 on the other surface.
[0552] In the touch panel 90, the routing wiring 56 is connected to each of the first transparent electrode pattern 70 and the second transparent electrode pattern 72. The routing wiring 56 is, for example, a copper wiring.
[0553] In the touch panel 90 , a touch panel electrode protection film 18 is formed on a surface on one side of the substrate 32 in a manner that covers the first transparent electrode pattern 70 and the bypass wiring 56 , and a touch panel electrode protection film 18 is formed on a surface on the other side of the substrate 32 in a manner that covers the second transparent electrode pattern 72 and the bypass wiring 56 .
[0554] The first refractive index adjustment layer and the second refractive index adjustment layer in the first specific example may be formed on one surface and the other surface of the substrate 32 , respectively.
[0555] [Method for manufacturing touch panel]
[0556] The manufacturing method of the touch panel of the present invention comprises:
[0557] a first peeling step of peeling off the protective film from the transfer film of the present invention;
[0558] a transfer step of transferring the transfer film from which the protective film has been peeled off from the photosensitive resin layer side onto a touch panel substrate having a structure in which at least one of a touch panel electrode and a touch panel wiring is arranged on the substrate;
[0559] an exposure step of exposing the transferred photosensitive resin layer to pattern exposure;
[0560] A second peeling step of peeling off the temporary support after the exposure step; and
[0561] After the second peeling step, the pattern-exposed photosensitive resin layer is developed to obtain a touch panel protective film that protects at least a portion of at least one of the touch panel electrodes and the touch panel wiring.
[0562] [First peeling step]
[0563] The first peeling step is a step of peeling the protective film from the transfer film of the present invention described above. The peeling method is not particularly limited, and a known method can be appropriately adopted.
[0564] 〔Transfer process〕
[0565] The transfer step is a step of transferring the transfer film from which the protective film has been peeled off, from the photosensitive resin layer side onto a touch panel substrate having a structure in which at least one of a touch panel electrode and a touch panel wiring is arranged on the substrate.
[0566] As a transfer method, there can be cited a method of laminating the above-mentioned transfer film of the present invention on at least one configuration side of the touch panel electrodes and touch panel wiring of the touch panel substrate, transferring the photosensitive resin layer in the transfer film to the above-mentioned surface, thereby forming a photosensitive resin layer on the above-mentioned surface.
[0567] Lamination (so-called transfer of the photosensitive resin layer) can be performed using a known laminator such as a vacuum laminator and an automatic cutting laminator.
[0568] As lamination conditions, general conditions can be applied.
[0569] The lamination temperature is preferably 80°C to 150°C, more preferably 90°C to 150°C, and further preferably 100°C to 150°C.
[0570] When a laminator equipped with a rubber roller is used, the lamination temperature refers to the temperature of the rubber roller.
[0571] The substrate temperature during lamination is not particularly limited.
[0572] The substrate temperature during lamination is preferably 10°C to 150°C, more preferably 20°C to 150°C, and even more preferably 30°C to 150°C.
[0573] When a resin substrate is used as the substrate, the substrate temperature during lamination is preferably 10°C to 80°C, more preferably 20°C to 60°C, and further preferably 30°C to 50°C.
[0574] Furthermore, the linear pressure during lamination is preferably 0.5 N / cm to 20 N / cm, more preferably 1 N / cm to 10 N / cm, and even more preferably 1 N / cm to 5 N / cm.
[0575] Furthermore, the conveying speed during lamination (lamination speed) is preferably 0.5 m / min to 5 m / min, and more preferably 1.5 m / min to 3 m / min.
[0576] Through the transfer process, the photosensitive resin layer of the transfer film is transferred to the surface of the touch panel substrate on the side where the electrodes are arranged, thereby forming a laminate having a laminate structure of temporary support body / thermoplastic resin layer / photosensitive resin layer / electrodes / substrate. In this laminate structure, the "electrodes / substrate" portion is the touch panel substrate.
[0577] [Exposure process]
[0578] The exposure step is a step of exposing the transferred photosensitive resin layer to pattern exposure.
[0579] Here, pattern exposure means exposure in a pattern-like manner, that is, exposure in which exposed portions and non-exposed portions exist.
[0580] In the photosensitive resin layer on the touch panel substrate, the exposed portion in the pattern exposure is cured to finally form a cured film.
[0581] On the other hand, in the photosensitive resin layer on the touch panel substrate, the non-exposed portion during the pattern exposure is not cured, but is dissolved and removed by the developer in the subsequent development step. The non-exposed portion can form an opening of the cured film after the development step.
[0582] The pattern exposure may be exposure through a mask or may be digital exposure using a laser or the like.
[0583] As the light source for pattern exposure, any light having a wavelength region (for example, 365 nm or 405 nm) can be appropriately selected and used as long as it is light that can irradiate the curable photosensitive resin layer.
[0584] Examples of the light source include various lasers, light emitting diodes (LEDs), ultrahigh pressure mercury lamps, high pressure mercury lamps, and metal halide lamps.
[0585] The exposure dose is preferably 5 mJ / cm 2 ~200mJ / cm 2, more preferably 10 mJ / cm 2 ~200mJ / cm 2 .
[0586] [Second peeling step]
[0587] The second peeling step is a step of peeling the temporary support after the exposure step. The peeling method is not particularly limited, and a known method can be appropriately adopted.
[0588] 〔Development process〕
[0589] The development step is a step of developing the pattern-exposed photosensitive resin layer after the second peeling step to obtain a touch panel protective film that protects at least a portion of at least one of the touch panel electrodes and the touch panel wiring.
[0590] The developer used for development is not particularly limited, and a known developer such as the developer described in Japanese Patent Application Laid-Open No. 5-72724 can be used.
[0591] As the developer, an alkaline aqueous solution is preferably used.
[0592] Examples of the alkaline compound that may be contained in the alkaline aqueous solution include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and choline (2-hydroxyethyltrimethylammonium hydroxide).
[0593] The pH of the alkaline aqueous solution at 25°C is preferably 8 to 13, more preferably 9 to 12, and particularly preferably 10 to 12.
[0594] The content of the basic compound in the basic aqueous solution is preferably 0.1% by mass to 5% by mass, more preferably 0.1% by mass to 3% by mass, relative to the total mass of the basic aqueous solution.
[0595] The developer may contain an organic solvent having miscibility with water.
[0596] Examples of the organic solvent include methanol, ethanol, 2-propanol, 1-propanol, butanol, diacetone alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-butyl ether, benzyl alcohol, acetone, methyl ethyl ketone, cyclohexanone, ε-caprolactone, γ-butyrolactone, dimethylformamide, dimethylacetamide, hexamethylphosphoramide, ethyl lactate, methyl lactate, ε-caprolactam, and N-methylpyrrolidone.
[0597] The concentration of the organic solvent is preferably 0.1% by mass to 30% by mass.
[0598] The developer may contain a known surfactant.
[0599] The concentration of the surfactant is preferably 0.01% by mass to 10% by mass.
[0600] The liquid temperature of the developer is preferably 20°C to 40°C.
[0601] Examples of the method of development include spin coating immersion development, shower development, shower and spin development, and immersion development.
[0602] When shower development is performed, a developer is sprayed in a shower on the photosensitive resin layer after pattern exposure to remove the non-exposed portion of the photosensitive resin layer.
[0603] When using a transfer film having a photosensitive resin layer and at least one of a thermoplastic resin layer and an intermediate layer, after transferring these layers onto a substrate and before developing the photosensitive resin layer, an alkaline solution with low solubility in the photosensitive resin layer can be sprayed in a spray-like manner to pre-remove at least one of the thermoplastic resin layer and the intermediate layer (or two when there are two).
[0604] Furthermore, after development, it is preferable to remove development residues by spraying a cleaning agent or the like with a shower and wiping with a brush or the like.
[0605] The liquid temperature of the developer is preferably 20°C to 40°C.
[0606] The development step may include a step of performing the development described above and a step of subjecting the cured film obtained by the development described above to a heat treatment (hereinafter also referred to as “post-baking”).
[0607] When the substrate is a resin substrate, the temperature of the post-bake is preferably 100°C to 160°C, more preferably 130°C to 160°C.
[0608] This post-baking can also adjust the resistance value of the transparent electrode pattern.
[0609] When the photosensitive resin layer contains a carboxyl group-containing (meth)acrylic resin, at least a portion of the carboxyl group-containing (meth)acrylic resin can be converted to carboxylic anhydride by post-baking. Such a conversion provides excellent developability and cured film strength.
[0610] The development process may include a step of performing the development described above and a step of exposing the cured film obtained by the development described above (hereinafter also referred to as “post-exposure”).
[0611] When the development process includes two steps of a post-exposure step and a post-baking step, it is preferable to perform the post-baking after the post-exposure step.
[0612] Regarding pattern exposure, development, and the like, for example, reference can be made to the description in paragraphs 0035 to 0051 of Japanese Patent Application Laid-Open No. 2006-23696.
[0613] The pattern (cured film of the photosensitive resin layer) formed by the above steps is preferably achromatic.
[0614] Specifically, total reflection (incident angle 8°, light source: D-65 (2° field of view)) is in CIE1976 (L * , a * , b * ) color space, the pattern’s L * The value is preferably 10 to 90, and the pattern a * The value is preferably -1.0 to 1.0, and the b * The value is preferably -1.0 to 1.0.
[0615] The method for manufacturing a touch panel according to the present invention may include steps other than the steps described above (so-called other steps).
[0616] As other steps, there can be mentioned known steps (for example, a cleaning step) which are sometimes provided in a general photolithography step.
[0617] [Example]
[0618] The present invention is further specifically described by giving examples below. The materials, usage amounts, ratios, processing contents, processing steps etc. shown in the following examples can be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. In addition, "parts", "%" are mass references unless otherwise specified.
[0619] In the following examples, the weight average molecular weight of the resin is the weight average molecular weight calculated in terms of polystyrene by gel permeation chromatography (GPC). Also, the acid value is the theoretical acid value.
[0620] <Preparation of coating solution for forming photosensitive resin layer>
[0621] Materials A-1 to A-7 as coating solutions for forming a photosensitive resin layer were prepared to have the compositions shown in Table 1 below, respectively.
[0622] [Table 1]
[0623]
[0624] MAA-GMA: A structural unit obtained by adding glycidyl methacrylate to a structural unit derived from methacrylic acid.
[0625] <Preparation of coating liquid for forming refractive index adjusting layer>
[0626] Material B-1 as a coating liquid for forming a refractive index adjusting layer was prepared to have the composition shown in Table 2 below.
[0627] [Table 2]
[0628]
[0629] [Example 1]
[0630] The photosensitive resin layer was formed by applying the material A-1 for forming the photosensitive resin layer using a slit-shaped nozzle on a polyethylene terephthalate film (temporary support) having a total thickness of 16 μm, in which a polyethylene terephthalate layer (particle-containing layer) having a thickness of 1 μm and containing 0.05 mass % of calcium carbonate (average particle diameter: 1.0 μm) was provided on both sides of a polyethylene terephthalate layer having a thickness of 14 μm. In addition, the coating amount was adjusted so that the film thickness after drying would be the thickness shown in Table 3 below.
[0631] Next, after the solvent was volatilized in a drying zone at 100°C, a polypropylene layer (particle-containing layer) with a thickness of 1 μm and containing 0.05 mass % of calcium carbonate (average particle size: 1.0 μm) was crimped onto the photosensitive resin layer, and a polypropylene film (protective film) with a total thickness of 30 μm was set on both sides of a polypropylene layer with a thickness of 28 μm, thereby producing the transfer film of Example 1.
[0632] [Examples 2 to 4, Example 8 and Comparative Example 1]
[0633] A transfer film was prepared in the same manner as in Example 1 except that the material A-1 for forming the photosensitive resin layer was changed to a material shown in Table 3 below.
[0634] [Example 5]
[0635] A transfer film was prepared in the same manner as in Example 1 except that the material A-1 for forming the photosensitive resin layer was changed to a material shown in Table 3 below and the concentration of calcium carbonate contained in the particle-containing layer in the temporary support and the protective film was changed so as to satisfy the arithmetic mean roughness Ra shown in Table 3 below.
[0636] [Example 6]
[0637] The refractive index adjusting layer forming material B-1 was applied onto the photosensitive resin layer formed in the same manner as in Example 1 using a slit nozzle and dried at 80° C. to form a refractive index adjusting layer. The coating amount was adjusted so that the film thickness after drying was 70 nm.
[0638] Next, a polyethylene terephthalate film (protective film) having a thickness of 16 μm was pressure-bonded onto the refractive index adjusting layer, thereby producing a transfer film of Example 6.
[0639] The refractive index of the refractive index adjusting layer is 1.68.
[0640] [Example 7]
[0641] A transfer film was prepared in the same manner as in Example 5 except that the concentrations of calcium carbonate contained in the temporary support and the particle-containing layer in the protective film were changed so as to satisfy the arithmetic mean roughness Ra shown in Table 3 below.
[0642] [Comparative Example 2]
[0643] A transfer film was prepared in the same manner as in Example 1 except that the concentration of calcium carbonate contained in the particle-containing layer in the temporary support was changed so as to satisfy the arithmetic mean roughness Ra shown in Table 3 below.
[0644] [Comparative Example 3]
[0645] A transfer film was prepared in the same manner as in Example 1 except that the concentration of calcium carbonate contained in the particle-containing layer in the protective film was changed so as to satisfy the arithmetic mean roughness Ra shown in Table 3 below.
[0646] [Evaluation of water vapor permeability (moisture permeability)]
[0647] The moisture permeability (average value) was measured by the above-mentioned method.
[0648] The water vapor permeability was evaluated based on the average value of the measured water vapor permeability according to the following evaluation criteria. In the following evaluation criteria, as long as it is A or B, it is suitable for practical use. The results are recorded in the item of the photosensitive resin layer in Table 3 below.
[0649] In the above measurement, the moisture permeability of the circular sample having the laminated structure of the cured film / membrane filter was measured as described above. However, the moisture permeability of the membrane filter is extremely high compared to the moisture permeability of the cured film, so in the above measurement, the moisture permeability of the cured film itself of the photosensitive resin layer is actually measured.
[0650] (Evaluation criteria for water vapor permeability)
[0651] A: The average moisture permeability is less than 400g / m 2 / 24hr
[0652] B: The average moisture permeability is 400g / m 2 / 24hr or more and less than 500g / m 2 / 24hr
[0653] C: The average moisture permeability is 500g / m 2 / 24hr or more
[0654] 〔Measurement of elongation at break〕
[0655] The elongation at break of the cured film of the photosensitive resin layer at 23° C. and 120° C. was measured by the above method. The results are described in the item of the photosensitive resin layer in Table 3 below.
[0656] [Measurement of arithmetic mean roughness Ra]
[0657] The surface of the photosensitive resin layer side of the protective film peeled from the transfer film prepared in the examples and comparative examples was exposed to light at an exposure dose of 100 mJ / cm2 via a temporary support using a proximity exposure type exposure machine (manufactured by Hitachi High-Tech Electronics Engineering Co., Ltd.) equipped with an ultra-high pressure mercury lamp. 2 The arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of the temporary support peeled off after the photosensitive resin layer was exposed (i-ray) was measured.
[0658] The measurement was performed using an optical surface property measuring instrument (Zygo NewView 6300 (manufactured by Zygo Corporation)). The results are shown in Table 3 below.
[0659] [Table 3]
[0660]
[0661] [Production of transparent electrode pattern film]
[0662] <Formation of Transparent Film>
[0663] A cycloolefin resin film with a thickness of 38 μm and a refractive index of 1.53 was subjected to corona discharge treatment for 3 seconds using a high frequency oscillator at an output voltage of 100%, an output power of 250 W, a wire electrode with a diameter of 1.2 mm, an electrode length of 240 mm, and a distance of 1.5 mm between working electrodes, and surface modification was performed. The obtained film was made into a transparent film substrate.
[0664] Next, the material C shown in Table 4 below was applied onto the transparent film substrate using a slit nozzle, and then irradiated with ultraviolet light (accumulated light amount 300 mJ / cm 2 ), and dried at about 110° C. to produce a transparent film having a refractive index of 1.60 and a film thickness of 80 nm.
[0665] [Table 4]
[0666]
[0667] [Chemical formula 22]
[0668]
[0669] <Formation of Transparent Electrode Pattern>
[0670] The film with the transparent film laminated on the transparent film substrate obtained above was introduced into a vacuum chamber, and an ITO target (indium: tin = 95:5 (molar ratio)) with a SnO2 content of 10% by mass was used to form an ITO film with a thickness of 40nm and a refractive index of 1.82 by direct current (DC) magnetron sputtering (conditions: temperature of the transparent film substrate 150°C, argon partial pressure 0.13Pa, oxygen partial pressure 0.01Pa), and a film in which a transparent film and a transparent electrode layer were formed on the transparent film substrate was obtained. The surface resistance of the ITO film was 80Ω / mouth (per square Ω).
[0671] <Preparation of Photosensitive Film E1 for Etching>
[0672] A thermoplastic resin layer coating liquid having the following prescription H1 was applied onto a 75 μm thick polyethylene terephthalate film temporary support using a slit nozzle and dried.
[0673] Next, an intermediate layer coating liquid having the following formulation P1 was applied and dried.
[0674] In addition, a coating liquid for etching photocurable resin layer composed of the following prescription E1 is applied and dried. By the method described above, a laminate consisting of a thermoplastic resin layer with a dry film thickness of 15.1 μm, an intermediate layer with a dry film thickness of 1.6 μm, and an etching photocurable resin layer with a film thickness of 2.0 μm is prepared on a temporary support, and finally a protective film (polypropylene film with a thickness of 12 μm) is crimped. In this way, an etching photosensitive film E1 as a transfer material in which a temporary support, a thermoplastic resin layer, an intermediate layer (oxygen barrier film) and an etching photocurable resin layer are integrated is prepared.
[0675] (Coating liquid for thermoplastic resin layer: Prescription H1)
[0676] Methanol: 11.1 parts by mass
[0677] Propylene glycol monomethyl ether acetate: 6.36 parts by mass
[0678] Methyl ethyl ketone: 52.4 parts by mass
[0679] Methyl methacrylate / 2-ethylhexyl acrylate / benzyl methacrylate / methacrylic acid copolymer (copolymer composition ratio (molar ratio) = 55 / 11.7 / 4.5 / 28.8, molecular weight = 100,000, Tg≈70°C: 5.83 parts by mass
[0680] Styrene / acrylic acid copolymer (copolymer composition ratio (molar ratio) = 63 / 37, weight average molecular weight = 10,000, Tg ≈ 100°C): 13.6 parts by mass
[0681] Monomer 1 (trade name: BPE-500, manufactured by Shin-Nakamura Chemical Co., Ltd.): 9.1 parts by mass
[0682] Fluorine-based polymer [the following components]: 0.54 parts by mass
[0683] Fluorine polymer: C6F 13 A copolymer of 40 parts by mass of CH2CH2OCOCH=CH2, 55 parts by mass of (OCH(CH3)CH2)7OCOCH=CH2 and 5 parts by mass of H(OCHCH2)7OCOCH=CH2 (weight average molecular weight 30,000, 30% by mass solution in methyl ethyl ketone, trade name: MEGAFACE F780F, manufactured by DIC Corporation)
[0684] (Intermediate layer coating liquid: prescription P1)
[0685] Polyvinyl alcohol (trade name: PVA205, manufactured by KURARAY CO., LTD., saponification degree = 88%, polymerization degree 550): 32.2 parts by mass
[0686] Polyvinyl pyrrolidone (trade name: K-30, manufactured by ISP Japan Co., Ltd.): 14.9 parts by mass
[0687] Distilled water: 524 parts by mass
[0688] Methanol: 429 parts by mass
[0689] (Coating liquid for etching photocurable resin layer: Prescription E1)
[0690] Methyl methacrylate / styrene / methacrylic acid copolymer (copolymer composition ratio (mass %): 31 / 40 / 29, weight average molecular weight 60,000, acid value 163 mgKOH / g): 16 parts by mass.
[0691] Monomer 1 (trade name: BPE-500, manufactured by Shin-Nakamura Chemical Co., Ltd.): 5.6 parts by mass
[0692] · 0.5 mol adduct of hexamethylene diisocyanate and ethylene tetraoxide monomethacrylate: 7 parts by mass
[0693] Cyclohexanedimethanol monoacrylate as a compound having one polymerizable group in the molecule: 2.8 parts by mass
[0694] 2-Chloro-N-butylacridone: 0.42 parts by mass
[0695] 2,2-Bis(O-chlorophenyl)-4,4',5,5'-tetraphenylbiimidazole: 2.17 parts by mass
[0696] Malachite green oxalate: 0.02 parts by mass
[0697] Colorless crystal violet: 0.26 parts by mass
[0698] Phenothiazine: 0.013 parts by mass
[0699] Surfactant (trade name: MEGAFACE F-780F, manufactured by DIC Corporation): 0.03 parts by mass
[0700] Methyl ethyl ketone: 40 parts by mass
[0701] 1-Methoxy-2-propanol: 20 parts by mass
[0702] The viscosity of the etching photocurable resin layer coating liquid E1 at 100° C. after the solvent was removed was 2,500 Pa·sec.
[0703] <Formation of Transparent Electrode Pattern>
[0704] The transparent film substrate on which the transparent film and the transparent electrode layer were formed was cleaned and the etching photosensitive film E1 obtained by removing the protective film was laminated. The lamination conditions were transparent film substrate temperature: 130°C, rubber roller temperature: 120°C, linear pressure: 100 N / cm, and conveying speed: 2.2 m / min.
[0705] After the temporary support was peeled off, the distance between the exposure mask (quartz exposure mask having a transparent electrode pattern) and the above-mentioned curable resin layer for etching was set to 200 μm, and the exposure amount was 50 mJ / cm 2 (i-ray) for pattern exposure.
[0706] Next, a triethanolamine-based developer (containing 30% by mass of triethanolamine, a solution obtained by diluting trade name: T-PD2 (manufactured by Fujifilm Corporation) by 10 times with pure water) was treated at 25°C for 100 seconds, and a surfactant-containing cleaning solution (a solution obtained by diluting trade name: T-SD3 (manufactured by Fujifilm Corporation) by 10 times with pure water) was treated at 33°C for 20 seconds. Residues were removed using a rotating brush and an ultra-high pressure cleaning nozzle, and a post-baking treatment was performed at 130°C for 30 minutes to obtain a film having a transparent film, a transparent electrode layer, and a photocurable resin layer pattern formed on a transparent film substrate.
[0707] A film having a transparent film, a transparent electrode layer and an etching photocurable resin layer pattern formed on a transparent film substrate is immersed in an etching tank filled with an ITO etching solution (hydrochloric acid, potassium chloride aqueous solution, liquid temperature 30° C.) and treated for 100 seconds, and the transparent electrode layer in the exposed area not covered by the etching photocurable resin layer is dissolved and removed, thereby obtaining a film with a transparent electrode pattern having an etching photocurable resin layer pattern.
[0708] Next, the film with a transparent electrode pattern having a photocurable resin layer pattern for etching was immersed in a resist stripping tank filled with a resist stripping solution (N-methyl-2-pyrrolidone, monoethanolamine, surfactant (trade name: Surfynol 465, manufactured by Air Products and Chemicals, Inc.), liquid temperature 45°C) and treated for 200 seconds to remove the photocurable resin layer for etching, thereby obtaining a film having a transparent film and a transparent electrode pattern formed on a transparent film substrate.
[0709] [Production of laminated body]
[0710] Using the transfer films of Examples and Comparative Examples from which the protective films were peeled off, the transparent film and the transparent electrode pattern formed on the transparent film substrate were transferred to the position covered by the transfer film.
[0711] As a result, the photosensitive resin layer and the temporary support were sequentially transferred onto the transparent film and the transparent electrode pattern of the transparent film substrate through the transfer film. In Example 6, the refractive index adjustment layer, the photosensitive resin layer and the temporary support were sequentially transferred. The transfer was performed using a vacuum laminator manufactured by MCK CO., LTD, under the conditions of a transparent film substrate temperature of 40°C, a rubber roller temperature of 100°C, a linear pressure of 3 N / cm, and a conveying speed of 2 m / min.
[0712] Then, a proximity exposure type exposure machine (manufactured by Hitachi High-Tech Electronics Engineering Co., Ltd.) equipped with an ultra-high pressure mercury lamp was used to bring the exposure mask (quartz exposure mask having a pattern for forming an electrode protective film) into close contact with the temporary support, and an exposure dose of 100 mJ / cm was applied through the temporary support. 2 (i-ray) pattern exposure was performed.
[0713] After the temporary support was peeled off, a development treatment was performed at 32° C. for 60 seconds using a 1% sodium carbonate aqueous solution.
[0714] Thereafter, ultrapure water was sprayed from an ultrahigh pressure cleaning nozzle toward the transparent film substrate after the development process to remove the residue.
[0715] Subsequently, air was blown in to remove moisture from the transparent film substrate, and post-baking was performed at 145° C. for 30 minutes, thereby forming a laminated body in which a transparent film, a transparent electrode pattern, and a cured product of a photosensitive resin layer were sequentially stacked on the transparent film substrate from the substrate. In Example 6, a laminated body in which a transparent film, a transparent electrode pattern, a refractive index adjustment layer, and a cured product of a photosensitive resin layer were sequentially stacked on the transparent film substrate from the substrate was formed.
[0716] 〔Stamping processability〕
[0717] The produced laminated body was evaluated for punching workability during punching.
[0718] The Thomson knife was set to punch a 10 cm square shape, and after punching at a temperature of 120° C., the cut portion was evaluated using an optical microscope according to the following criteria. The results are shown in Table 5. In addition, if the evaluation is A or B, it can be evaluated that there is no problem in practical use.
[0719] A: No chips or cracks on any side.
[0720] B: Slight notches and cracks
[0721] C: Obvious gaps and cracks
[0722] 〔Peelability〕
[0723] (Removability of protective film)
[0724] Whether or not peeling failure occurred when the protective film was peeled off before transfer was evaluated based on the following criteria. The results are shown in Table 5 below.
[0725] A: The photosensitive resin layer did not remain on the protective film side, and no abnormality was observed in the photosensitive resin layer.
[0726] B: A small amount of the photosensitive resin layer was observed to remain on the protective film side at the start of peeling, but other than that, there were no problems and there was no problem in practical use.
[0727] C: Residue of the photosensitive resin layer was significantly generated on the protective film side, which caused problems in practical use.
[0728] (Removability of temporary support)
[0729] Whether or not peeling failure occurred when the temporary support was peeled off after exposure and before development was evaluated based on the following criteria. The results are shown in Table 5 below.
[0730] A: The photosensitive resin layer does not remain on the temporary support side, and no abnormality is observed in the photosensitive resin layer.
[0731] B: A small amount of the photosensitive resin layer was observed to remain on the temporary support side at the start of peeling, but other than that, there were no problems and there was no problem in practical use.
[0732] C: Residue of the photosensitive resin layer was significantly generated on the temporary support side, which caused problems in practical use.
[0733] [Table 5]
[0734]
[0735] As shown in the results in Tables 3 and 5, it is found that when the photosensitive resin layer has a breaking elongation of less than 15% at 120° C. after curing, the punching processability is poor (Comparative Example 1).
[0736] Furthermore, it was found that even if the photosensitive resin layer had a breaking elongation of 15% or more at 120°C after curing, the temporary support had poor releasability if the arithmetic mean roughness Ra of the surface on the photosensitive resin layer side exceeded 50 nm (Comparative Example 2).
[0737] Furthermore, even if the photosensitive resin layer has a breaking elongation of 15% or more at 120°C after curing, the protective film has poor releasability if the arithmetic mean roughness Ra of the surface on the photosensitive resin layer side of the protective film exceeds 150 nm (Comparative Example 3).
[0738] In contrast, if the photosensitive resin layer has a breaking elongation of 15% or more at 120°C after curing, the arithmetic mean roughness Ra of the surface of the temporary support on the photosensitive resin layer side is less than 50nm, and the arithmetic mean roughness Ra of the surface of the protective film on the photosensitive resin layer side is less than 150nm, then the temporary support and the protective film have excellent releasability, and the cured film formed by curing and transferring the photosensitive resin layer has excellent stamping processability (Examples 1 to 8).
[0739] Explanation of symbols
[0740] 1-sample, 2-chuck portion, 10-transfer film, 12-temporary support body, 16-protective film, 18-touch panel electrode protective film, 18A-photosensitive resin layer, 20-first refractive index adjustment layer, 20A-refractive index adjustment layer, 30-touch panel, 32-substrate, 34-transparent electrode pattern, 36-second refractive index adjustment layer, 40-first area where transparent electrode pattern exists, 42-second area where transparent electrode pattern does not exist, 56-circuit wiring, 70-first transparent electrode pattern, 72-second transparent electrode pattern, 74-image display area, 75-image non-display area, 90-touch panel.
Claims
1. A transfer film comprising a temporary support, a photosensitive resin layer and a protective film in this order, wherein: The cured film formed by curing the photosensitive resin layer has a breaking elongation of 15% or more at 120° C., The arithmetic mean roughness Ra of the surface of the temporary support on the photosensitive resin layer side is 50 nm or less, The arithmetic mean roughness Ra of the surface of the protective film on the photosensitive resin layer side is 150 nm or less, The transfer film satisfies the following formula (1): X×Y<400 Formula (1) Here, in the formula (1), X represents the breaking elongation value at 120° C. of a cured film obtained by curing the photosensitive resin layer, and the unit is %, and Y represents the arithmetic mean roughness Ra value of the surface of the temporary support on the photosensitive resin layer side, and the unit is nm.
2. The transfer film according to claim 1, which satisfies the following formula (2): Y≤Z Formula (2) Here, in the formula (2), Y represents the value of the arithmetic mean roughness Ra of the surface of the temporary support on the photosensitive resin layer side, in nm, and Z represents the value of the arithmetic mean roughness Ra of the surface of the protective film on the photosensitive resin layer side, in nm.
3. The transfer film according to claim 1 or 2, wherein The cured film formed by curing the photosensitive resin layer has a moisture permeability of 500 g / m 2 / 24hr or less.
4. The transfer film according to claim 1 or 2, wherein The elongation at break of a cured film obtained by curing the photosensitive resin layer at 120° C. is at least twice as large as the elongation at break at 23° C.
5. The transfer film according to claim 1 or 2, wherein The photosensitive resin layer contains a binder polymer, a polymerizable monomer, and a photopolymerization initiator.
6. The transfer film according to claim 5, wherein The acid value of the binder polymer is 30 mgKOH / g to 160 mgKOH / g.
7. The transfer film according to claim 5, wherein: The photosensitive resin layer further contains a compound that generates a group capable of reacting with an acid group or a hydroxyl group by heating.
8. The transfer film according to claim 5, wherein The photosensitive resin layer further contains a compound capable of undergoing a Michael addition reaction.
9. The transfer film according to claim 1, wherein A refractive index adjusting layer having a higher refractive index than the photosensitive resin layer is further provided between the photosensitive resin layer and the protective film. 10 . The transfer film according to claim 1 , which is used to form an electrode protection film.
11. A method for manufacturing a laminate, comprising: A first peeling step of peeling the protective film from the transfer film according to any one of claims 1 to 10; A transfer step of transferring the transfer film after peeling off the protective film from the photosensitive resin layer side to a substrate having an electrode; a curing step of curing at least a portion of the transferred photosensitive resin layer to form a cured film; and The second peeling step is to peel off the temporary support after the curing step to obtain a laminated body in which the cured film is laminated on the substrate having an electrode.
12. A method for manufacturing a touch panel, comprising: A first peeling step of peeling the protective film from the transfer film according to any one of claims 1 to 10; a transfer step of transferring the transfer film after peeling off the protective film from the photosensitive resin layer side to a touch panel substrate having a structure in which at least one of a touch panel electrode and a touch panel wiring is arranged on the substrate; An exposure step of exposing the transferred photosensitive resin layer in a pattern; A second peeling step of peeling off the temporary support after the exposure step; and A developing step of developing the pattern-exposed photosensitive resin layer after the second peeling step, thereby obtaining a touch panel protective film that protects at least a portion of at least one of the touch panel electrodes and the touch panel wirings.
Citation Information
Patent Citations
JP1973042965B1
Insatsuinki oyobi hifukuzairyonotameno hikarijugokanonaketsugozai
JP1976082102A
Photopolymerizable composition
JP1977134692A
JP1980034414B2
Coating composition and curing method
JP1984138205A